Polyester film with easy-adhesion layer, optical laminate including said polyester film, and polarizing plate, surface plate, image display panel, and image display device including said optical laminate

By forming a easily sticky layer with low δq/δa values ​​on the PET film, the problem of reducing the display effect caused by rainbow unevenness in the display device is solved, and the overall adhesion and scratch resistance of the film are improved.

JP7660711B2Active Publication Date: 2025-04-11DAI NIPPON PRINTING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023567189
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-02
Filing Date
2023-03-01
Publication Date
2025-04-11
Estimated Expiration
2043-03-01

AI Technical Summary

Technical Problem

When used in a display device for polarized light output, the PET film causes rainbow unevenness due to flat phase difference, which affects the display effect; while the method of reducing flat phase difference may lead to uneven pen hardness of the film, increase the risk of damage, and easily lead to peeling problems of the easily sticky layer.

Method used

A polyester film with B or higher pen hardness is used, and a sticky layer with an average δq/δa value of 1.60 or lower is formed on its surface to improve the overall adhesion of the optical film.

Benefits of technology

It effectively improves the adhesion of the optical film, reduces the display effect caused by rainbow unevenness, enhances the scratch-resistant hardness of the film, and reduces the peeling problem between the easily sticky layer and the functional layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660711000011
    Figure 0007660711000011
  • Figure 0007660711000012
    Figure 0007660711000012
  • Figure 0007660711000013
    Figure 0007660711000013
Patent Text Reader

Abstract

Provided is an easily-adhesive layer-including polyester film capable of imparting good adhesion properties to an optical laminate that has a polyester film having a high pencil hardness, an easily-adhesive layer, and a functional layer in the stated order. The easily-adhesive layer-including polyester film has an easily-adhesive layer on a polyester film. The pencil hardness of the polyester film is at least B, and the mean value of δq / δa of a surface of the easily-adhesive layer is at most 1.60. δa represents the arithmetic mean value of phase signals on the surface of the easily-adhesive layer, and δq represents the root mean square of the phase signal on the surface of the easily-adhesive layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a polyester film with an easy-adhesion layer, an optical laminate including the polyester film, and a polarizing plate, a face plate, and an image display device including the optical laminate. [Background technology]

[0002] In image display devices such as liquid crystal display devices, organic EL display devices, micro LED display devices, mini LED display devices, quantum dot display devices, and laser hologram display devices, various optical laminates are arranged for the purpose of improving image visibility and suppressing scratches on the device surface. In addition, optical laminates may be arranged on the surfaces of show windows and painting covers for the purpose of improving the visibility of items and protecting items. Many of these optical laminates are configured to have a functional layer on a plastic film. As the plastic film of the optical laminate, a triacetyl cellulose film with small optical anisotropy has been preferably used. In this specification, the "triacetyl cellulose film" may be referred to as a "TAC film".

[0003] However, TAC films have problems in terms of dimensional stability and mechanical strength, and these problems are particularly noticeable in image display devices with large screens. For this reason, polyester films such as polyethylene terephthalate films have been proposed as an alternative to TAC films. In this specification, "polyethylene terephthalate films" may be referred to as "PET films."

[0004] However, when a PET film is applied to an image display device that outputs polarized light, such as a liquid crystal display device or an organic EL display device, a rainbow-like interference pattern called rainbow unevenness occurs due to the in-plane retardation of the PET film, which causes a problem of reduced visibility. As a countermeasure against rainbow unevenness, a method for extremely increasing the in-plane retardation of a PET film has been proposed (for example, Patent Document 1).

[0005] A PET film with an extremely large in-plane retardation as in Patent Document 1 can be obtained by uniaxially stretching a PET film. However, uniaxially stretched films have problems such as being prone to tearing in the stretching direction.

[0006] Contrary to Patent Document 1, one possible measure to deal with rainbow unevenness is to reduce the in-plane retardation of the PET film. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2011-107198 A [Patent Document 2] JP 2012-32819 A [Patent Document 3] JP 2016-6530 A Summary of the Invention [Problem to be solved by the invention]

[0008] A PET film with a small in-plane retardation can be obtained, for example, by reducing the stretching ratio. However, a PET film with a low stretching ratio has a problem in that the orientation in the thickness direction becomes uneven, which reduces the pencil hardness and makes the film susceptible to scratches.

[0009] Further, examples of PET films having a small in-plane retardation include those disclosed in Patent Documents 2 and 3. The PET films of Patent Documents 2 and 3 have a small in-plane retardation compared to general-purpose biaxially stretched PET films, for example, by reducing the difference in stretching ratio between the MD direction, which is the machine direction, and the TD direction, which is the width direction.

[0010] A PET film in which the in-plane retardation is reduced without lowering the stretching ratio as in Patent Documents 2 and 3 is easy to increase the pencil hardness. Such a biaxially stretched PET film with high pencil hardness has poor adhesion of the easy-adhesion layer. For this reason, an optical laminate in which a functional layer is formed on an easy-adhesion layer of a biaxially stretched PET film with high pencil hardness has a problem that the interface between the PET film and the easy-adhesion layer is easily peeled off. The above problem can be solved by applying an easy-adhesion layer made of a material with excellent adhesion. However, the above solution has a limited range of options for the material of the easy-adhesion layer, which causes restrictions on product design, and is therefore poor in practicality. In addition, when optically designing the entire optical laminate, if an easy-adhesion layer made of a specific material is present on the PET film, material restrictions on the functional layer formed on the easy-adhesion layer also occur.

[0011] The present disclosure aims to provide a polyester film with an easy-adhesion layer that can improve the adhesion of an optical laminate having a polyester film with high pencil hardness, an easy-adhesion layer, and a functional layer in this order. The present disclosure also aims to provide an optical laminate including the polyester film, and a polarizing plate, a surface plate, and an image display device including the optical laminate. [Means for solving the problem]

[0012] In order to solve the above problems, the present disclosure provides the following [1] to [5]. [1] A polyester film with an easy-adhesion layer, the polyester film having an easy-adhesion layer on the polyester film, the polyester film having a pencil hardness of B or more, and an average value of δq / δa of the surface of the easy-adhesion layer being 1.60 or less. <Calculation of the average value of δq / δa> A 10 μm×10 μm area on the surface of the easy-adhesion layer is measured in phase mode with an atomic force microscope. The measurement results in a distribution of phase signals on the surface of the easy-adhesion layer. The unit of the phase signal is [deg]. The arithmetic mean value of the phase signal shown in the following formula 1 is denoted as δa, and the root mean square value of the phase signal shown in the following formula 2 is denoted as δq. (In the following formulas 1 and 2, the orthogonal coordinate axes X and Y are placed on a reference surface indicating the average value of the phase signal, the axis perpendicular to the reference surface is the Z axis, and the curved surface of the phase signal is f(x, y). In the following formulas 1 and 2, the sizes of the regions for calculating δa and δq are Lx and Ly. In the following formulas 1 and 2, Ar=Lx×Ly.) Seven measurement evaluation areas of 2 μm × 2 μm are selected from the measurement area of ​​10 μm × 10 μm. Calculate δa, δq, and δq / δa for each of the seven measurement evaluation areas. Calculate the average value of δq / δa based on the five δq / δa values ​​excluding the maximum and minimum values ​​from the seven δq / δa values.

number

number

[0013] [2] An optical laminate having one or more functional layers on the easy-adhesion layer of the polyester film described in [1]. [3] A polarizing plate having a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical laminate described in [2], and the optical laminate is arranged so that the surface on the functional layer side faces away from the polarizer. [4] A surface plate having an optical laminate bonded to a resin plate or a glass plate, the optical laminate being the optical laminate described in [2], and the optical laminate being arranged so that the surface on the functional layer side faces the opposite side to the resin plate or the glass plate. [5] An image display device comprising the optical laminate according to [2] disposed on a display element. Effect of the Invention

[0014] The polyester film with an easy-adhesion layer of the present disclosure can improve the adhesion of an optical laminate having a polyester film with high pencil hardness, an easy-adhesion layer, and a functional layer in this order, without using a specific material for the easy-adhesion layer. The optical laminate of the present disclosure can improve the adhesion of the optical laminate, despite the high pencil hardness of the polyester film. The polarizing plate, surface plate, and image display device of the present disclosure have an optical laminate with good adhesion, and therefore can suppress defects due to poor adhesion of the optical laminate. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic diagram of an embodiment of an optical laminate according to the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an erosion rate measuring device. [Diagram 3] FIG. 2 is an image diagram of a polyester film being abraded by a test liquid containing pure water and spherical silica sprayed from a spray unit. [Figure 4] FIG. 13 is a diagram for explaining an example of a method for selecting multiple measurement regions of 10 μm×10 μm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The polyester film with an easy-adhesion layer, the optical laminate, the polarizing plate, the surface plate, and the image display device according to the present disclosure will be described below. In this specification, the expression "AA to BB" as a numerical range means "not less than AA and not more than BB."

[0017] [Optical laminate] The polyester film with an easy-adhesion layer of the present disclosure has an easy-adhesion layer on a polyester film, the polyester film having a pencil hardness of B or more, and an average value of δq / δa on the surface of the easy-adhesion layer of 1.60 or less. <Calculation of the average value of δq / δa> A 10 μm×10 μm area on the surface of the easy-adhesion layer is measured in phase mode with an atomic force microscope. The measurement results in a distribution of phase signals on the surface of the easy-adhesion layer. The unit of the phase signal is [deg]. The arithmetic mean value of the phase signal shown in the following formula 1 is denoted as δa, and the root mean square value of the phase signal shown in the following formula 2 is denoted as δq. (In the following formulas 1 and 2, the orthogonal coordinate axes X and Y are placed on a reference surface indicating the average value of the phase signal, the axis perpendicular to the reference surface is the Z axis, and the curved surface of the phase signal is f(x, y). In the following formulas 1 and 2, the sizes of the regions for calculating δa and δq are Lx and Ly. In the following formulas 1 and 2, Ar=Lx×Ly.) Seven measurement evaluation areas of 2 μm × 2 μm are selected from the measurement area of ​​10 μm × 10 μm. Calculate δa, δq, and δq / δa for each of the seven measurement evaluation areas. Calculate the average value of δq / δa based on the five δq / δa values ​​excluding the maximum and minimum values ​​from the seven δq / δa values.

[0018]

number

[0019]

number

[0020] <Polyester film> The polyester film must have a pencil hardness of B or higher. When the pencil hardness of the polyester film is less than B, the adhesion between the polyester film and the easy-adhesion layer is easily improved, and therefore the adhesion of the optical laminate as a whole is also easily improved. However, when the pencil hardness of the polyester film is less than B, the surface of the functional layer of the optical laminate or the polyester film itself is easily damaged, and the quality of the optical laminate is easily deteriorated. The polyester film with an easy-adhesion layer of the present disclosure has a pencil hardness of the polyester film of B or more. Therefore, it is easy to improve the scratch resistance of an optical laminate having a functional layer formed on the easy-adhesion layer. In addition, although the polyester film with an easy-adhesion layer of the present disclosure has a pencil hardness of B or more, the δq / δa of the surface of the easy-adhesion layer shows a predetermined value, so that the adhesion of the optical laminate can be improved. When the pencil hardness of the polyester film is B or higher, it is difficult to achieve good adhesion between the polyester film and the easy-adhesion layer. This is thought to be because polyester films with high pencil hardness tend to have high orientation, and the easy-adhesion layer does not easily penetrate into the highly oriented polyester film.

[0021] The pencil hardness of the polyester film is preferably HB or higher, and more preferably F or higher. If the pencil hardness of the polyester film is too high, the in-plane retardation of the polyester film tends to become large. By reducing the stretching ratio difference between the longitudinal and transverse directions of the polyester film, the in-plane retardation of the polyester film can be reduced. However, when the stretching ratio difference is reduced by reducing the stretching ratios in the longitudinal and transverse directions, it is difficult to make the pencil hardness of the polyester film HB or more. In addition, when the stretching ratio difference is reduced at a stretching ratio that results in a pencil hardness of more than 2H, the polyester film tends to become brittle in the film thickness direction because the orientation in the XY plane is high while the orientation in the Z axis direction is low. For this reason, the pencil hardness of the polyester film is preferably 2H or less.

[0022] In this specification, the pencil hardness is measured and determined according to the following procedures (1) to (6). (1) Prepare a sample by cutting a polyester film into a size of 5 cm x 10 cm. (2) Heat the polyester film at 100°C for 10 minutes. After heating, leave the polyester film to stand in an environment of 24°C and a relative humidity of 40% to 60% for 30 to 60 minutes. (Note: In the process of (2), make sure to keep the polyester film clean and flat. For example, when heating, hold one end of the film with a paper clip and hang it in the oven so that no strain is placed on the other end. Then, in the pencil hardness test of (3), perform the test on a part that is not touching the paper clip.) (3) A pencil hardness test is carried out on the polyester film. The pencil hardness test is carried out based on the scratch hardness (pencil method) of JIS K 5600-5-4:1999 as the standard, with modifications from the JIS regulations for the items specifically noted in (3) to (6). In the pencil hardness test, first, a pencil having a specified hardness is applied to the surface of the polyester film at an angle of 45°, and a load of 100 g is applied to the polyester film by moving the pencil at a speed of 3.0 mm / sec. (4) After applying a load to the polyester film, the sample is again heated at 100°C for 10 minutes. (5) Immediately after re-heating, the polyester film is visually inspected for scratches. The visual inspection environment is 24°C and the relative humidity is 40% to 60%. (6) The above steps (1) to (5) are repeated five times. The hardest pencil that does not scratch the polyester film four or more times out of the five is determined as the pencil hardness of the polyester film to be evaluated.

[0023] In the above-mentioned method for measuring and judging pencil hardness, if the pencil does not scratch four times out of five times with hardness B, and if the pencil does not scratch three times out of five times with hardness F, the pencil is judged to have a hardness of B.

[0024] When the polyester film has a slow axis and a fast axis, it is preferable that the pencil hardness is B or more in both the slow axis direction and the fast axis direction. The slow axis of the polyester film is the direction in the plane of the polyester film in which the refractive index is the highest. The fast axis of the polyester film is the direction perpendicular to the slow axis in the plane of the polyester film.

[0025] When the refractive index of the polyester film in the in-plane direction of the slow axis is defined as nx and the refractive index in the in-plane direction perpendicular to the slow axis is defined as ny, it is preferable that nx and ny satisfy the following relationship: nx-ny≦0.0250

[0026] By setting nx-ny to 0.0250 or less, it is possible to easily suppress rainbow unevenness caused by in-plane retardation. Depending on the design of the optical laminate, it is possible to easily suppress rainbow unevenness even when nx-ny is 0.0300 or less. In this specification, unless otherwise specified, rainbow unevenness refers to rainbow unevenness as seen with the naked eye. nx-ny is more preferably 0.0240 or less, and even more preferably 0.0230 or less.

[0027] If nx-ny is too small, it is difficult to suppress blackouts. Therefore, nx-ny is preferably 0.0050 or more, more preferably 0.0080 or more, more preferably 0.0100 or more, more preferably 0.0120 or more, and even more preferably 0.0130 or more. In this specification, blackout refers to a phenomenon in which the entire surface becomes dark when light that has passed through a polarizer and a polyester film in this order is viewed through a polarizer such as polarized sunglasses.

[0028] In the configuration elements shown in this specification, when multiple upper limit options and multiple lower limit options are shown, one selected from the upper limit options and one selected from the lower limit options can be combined to form an embodiment of the numerical range. For example, in the case of nx-ny, 0.0050 to 0.0300, 0.0050 to 0.0250, 0.0050 to 0.0240, 0.0050 to 0.0230, 0.0080 to 0.0300, 0.0080 to 0.0250, 0.0080 to 0.0240, 0.0080 to 0.0230, 0.0100 to 0.0300, 0.0100 to 0.0250, 0 Examples of embodiments include numerical ranges of 0.0100 or more and 0.0240 or less, 0.0100 or more and 0.0230 or less, 0.0120 or more and 0.0300 or less, 0.0120 or more and 0.0250 or less, 0.0120 or more and 0.0240 or less, 0.0120 or more and 0.0230 or less, 0.0130 or more and 0.0300 or less, 0.0130 or more and 0.0250 or less, 0.0130 or more and 0.0240 or less, and 0.0130 or more and 0.0230 or less.

[0029] In this specification, the refractive indexes such as nx and ny, the in-plane retardation, and the retardation in the thickness direction mean values ​​at a wavelength of 550 nm unless otherwise specified. In this specification, the "in-plane retardation" may be expressed as "Re", and the "retardation in the thickness direction" may be expressed as "Rth".

[0030] The nx-ny of the polyester film, as well as the in-plane retardation and thickness retardation described later, can be measured or calculated, for example, by Otsuka Electronics' product name "RETS-100". The nx-ny can be calculated if there is thickness information of the polyester film in addition to the measurement result of the in-plane retardation with the "RETS-100". The thickness retardation can be calculated if there is thickness information and average refractive index information of the polyester film in addition to the measurement result of the in-plane retardation with the "RETS-100" (for example, the average refractive index of polyethylene terephthalate is known to be 1.617, and this value is used for calculation in this specification). The thickness of the polyester film can be measured as follows. (1) For a polyester film having an easy-adhesion layer and a functional layer, a sample is first prepared with an exposed cross section of the polyester film so that cross-sectional observation can be performed. A microtome is used to prepare the sample. An example of a microtome is a Leica microtome. The thickness of the polyester film can be measured by observing the cross section with a scanning electron microscope. An example of a scanning electron microscope is Hitachi's "Model No. S4800." (2) The thickness of the polyester film having no adhesive layer or functional layer can be measured by a thickness gauge. An example of a thickness gauge is Nikon's DigiMicro. For Nikon's DigiMicro, it is preferable to use MS-5C and MH-15M as the stand and main body, and TC-101A as the counter.

[0031] In this specification, nx-ny, Re, and Rth mean the average values ​​of measurements taken at three points excluding the minimum and maximum values ​​of the five measurement points, unless otherwise specified. In this specification, the five measurement points are selected from any five points that are free of defects such as deformation, scratches, and dirt.

[0032] In this specification, the atmosphere in which various parameters are measured is set to a temperature of 23°C ± 5°C and a relative humidity of 40% to 65%, unless otherwise specified. Furthermore, the sample is exposed to the atmosphere for 30 minutes to 60 minutes before each measurement, unless otherwise specified. The various parameters include, for example, nx-ny, Re, Rth, δa, δq, total light transmittance, and haze.

[0033] The polyester film preferably has other physical properties such as an in-plane retardation and a retardation in the thickness direction within the following ranges. In this specification, the in-plane retardation and the retardation in the thickness direction are calculated by the following formula: In the following formula, "T" represents the thickness of the polyester film. In-plane phase difference (Re)=(nx-ny)×T[nm] Retardation in the thickness direction (Rth) = ((nx + ny) / 2 - nz) × T [nm]

[0034] -In-plane phase difference (Re)- The polyester film preferably has an in-plane retardation of 1200 nm or less, more preferably 1148 nm or less, more preferably 1100 nm or less, more preferably 1000 nm or less, and more preferably 950 nm or less. By setting the in-plane retardation to 1200 nm or less, it is possible to easily suppress rainbow unevenness. Rainbow unevenness can also be suppressed by adjusting the functional layer and the light source. In addition, there are applications in which rainbow unevenness is not important. For this reason, the in-plane retardation of the polyester film is not limited to 1200 nm or less, and may be more than 1200 nm.

[0035] The polyester film preferably has an in-plane retardation of 50 nm or more, more preferably 100 nm or more, more preferably 150 nm or more, more preferably 200 nm or more, more preferably 250 nm or more, more preferably 300 nm or more, more preferably 400 nm or more, more preferably 450 nm or more, and more preferably 497 nm or more. By making the in-plane retardation 50 nm or more, blackout can be easily suppressed. This is because a polyester film with an average in-plane retardation of less than 50 nm can hardly disturb linearly polarized light and transmits linearly polarized light as it is, while a polyester film with an average in-plane retardation of 50 nm or more can disturb linearly polarized light. In order to easily improve the pencil hardness of the polyester film, the in-plane retardation is preferably 520 nm or more, more preferably 620 nm or more.

[0036] Preferred ranges of the in-plane retardation are 50 nm or more and 1200 nm or less, 50 nm or more and 1148 nm or less, 50 nm or more and 1100 nm or less, 50 nm or more and 1000 nm or less, 50 nm or more and 950 nm or less, 100 nm or more and 1200 nm or less, 100 nm or more and 1148 nm or less, 100 nm or more and 1100 nm or less, 100 nm or more and 1000 nm or less, 100 nm or more and 950 nm or less, 150 nm or more and 120 0nm or less, 150nm or more and 1148nm or less, 150nm or more and 1100nm or less, 150nm or more and 1000nm or less, 150nm or more and 950nm or less, 200nm or more and 1200nm or less, 200nm or less Upper 1148nm or less, 200nm or more and 1100nm or less, 200nm or more and 1000nm or less, 200nm or more and 950nm or less, 250nm or more and 1200nm or less, 250nm or more and 1148nm or less, 250 nm to 1100nm, 250nm to 1000nm, 250nm to 950nm, 300nm to 1200nm, 300nm to 1148nm, 300nm to 1100nm , 300nm to 1000nm, 300nm to 950nm, 400nm to 1200nm, 400nm to 1148nm, 400nm to 1100nm, 400nm to 1000nm m or less, 400 nm or more and 950 nm or less, 450 nm or more and 1200 nm or less, 450 nm or more and 1148 nm or less, 450 nm or more and 1100 nm or less, 450 nm or more and 1000 nm or less, 450 nm or more and 950 nm or less, 497 nm or more and 1200 nm or less, 497 nm or more and 1148 nm or less, 497 nm or more and 1100 nm or less, 497 nm or more and 1000 nm or less, and 497 nm or more and 950 nm or less.

[0037] -Thickness direction phase difference (Rth)- The polyester film preferably has a thickness direction retardation of 2000 nm or more, more preferably 3000 nm or more, even more preferably 4000 nm or more, and even more preferably 5000 nm or more. By setting the retardation in the thickness direction of the polyester film to 2000 nm or more, it is possible to easily suppress blackout when viewed not only from the front direction but also from an oblique direction. The retardation in the thickness direction of the polyester film is preferably 15,000 nm or less, more preferably 12,000 nm or less, and further preferably 9,000 nm or less, so that Re / Rth can be easily set in the range described below.

[0038] Preferred embodiments of the retardation in the thickness direction include 2000 nm or more and 15000 nm or less, 2000 nm or more and 12000 nm or less, 2000 nm or more and 9000 nm or less, 3000 nm or more and 15000 nm or less, 3000 nm or more and 12000 nm or less, 3000 nm or more and 9000 nm or less, 4000 nm or more and 15000 nm or less, 4000 nm or more and 12000 nm or less, 4000 nm or more and 9000 nm or less, 5000 nm or more and 15000 nm or less, 5000 nm or more and 12000 nm or less, and 5000 nm or more and 9000 nm or less.

[0039] -Re / Rth- A small Re / Rth means that the degree of stretching of the polyester film approaches uniform biaxiality. Therefore, by making Re / Rth 0.20 or less, the pencil hardness of the polyester film can be easily improved. In addition, by making Re / Rth 0.20 or less, it is easy to suppress the polyester film from wrinkles caused by environmental changes, which adversely affects visibility. In order to easily exert the effect of making Re / Rth within a predetermined range, it is preferable that the in-plane retardation of the polyester film is within the above range. Re / Rth is more preferably 0.20 or less, more preferably 0.17 or less, and more preferably 0.15 or less. If Re / Rth is too small, the orientation in the XY plane is high, but the orientation in the Z axis direction is low, and the film tends to be brittle in the film thickness direction. Therefore, if Re / Rth is too small, the polyester film may break when the polyester film is attached to an adherend or peeled off from an adherend. Therefore, the polyester film preferably has Re / Rth of 0.01 or more, more preferably 0.03 or more, more preferably 0.05 or more, and more preferably 0.06 or more.

[0040] Preferred embodiments of the range of Re / Rth include 0.01 or more and 0.20 or less, 0.01 or more and 0.17 or less, 0.01 or more and 0.15 or less, 0.03 or more and 0.20 or less, 0.03 or more and 0.17 or less, 0.03 or more and 0.15 or less, 0.05 or more and 0.20 or less, 0.05 or more and 0.17 or less, 0.05 or more and 0.15 or less, 0.06 or more and 0.20 or less, 0.06 or more and 0.17 or less, and 0.06 or more and 0.15 or less.

[0041] -Haze, total light transmittance- The polyester film preferably has a haze according to JIS K7136:2000 of 3.0% or less, more preferably 2.0% or less, and even more preferably 1.0% or less. Furthermore, the polyester film preferably has a total light transmittance according to JIS K7361-1:1997 of 80% or more, more preferably 85% or more, and even more preferably 90% or more.

[0042] -UV transmittance- The polyester film preferably has a light transmittance of 20% or less at a wavelength of 380 nm, and more preferably has a light transmittance of 10% or less.

[0043] <Erosion rate> For polyester film, the average erosion rate from the surface to a depth of 20 μm is defined as E 0-20 When we define E 0-20 It is preferable that the surface roughness is 1.4 μm / g or more.

[0044] In this specification, E 0-20 is measured under the following measurement conditions. <Measurement conditions> A test liquid obtained by mixing pure water, a dispersion liquid, and spherical silica having an average particle size of 4.2 μm within ±8% at a mass ratio of 968:2:30 is stored in a container. The test liquid in the container is sent to a nozzle. Compressed air is sent into the nozzle to accelerate the test liquid in the nozzle, and a predetermined amount of the test liquid is sprayed perpendicularly to the polyester film from the nozzle tip nozzle, causing the spherical silica in the test liquid to collide with the polyester film. The cross-sectional shape of the nozzle is a square of 1 mm x 1 mm, and the distance between the nozzle hole and the polyester film is 4 mm. The flow rates of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are predetermined values ​​adjusted by calibration described later. After a predetermined amount of the test liquid has been sprayed, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, a cross-sectional profile is measured at the point on the polyester film where the spherical silica in the test liquid collided. The operation of three steps, which constitute one cycle, namely, a step of spraying a predetermined amount of the test liquid from the spray nozzle, a step of temporarily stopping the spraying of the test liquid after spraying the predetermined amount of the test liquid, and a step of measuring the cross-sectional profile after temporarily stopping the spraying of the test liquid, is performed until the depth of the cross-sectional profile exceeds 20 μm. Then, the erosion rate (μm / g) of the polyester film is calculated in each cycle until the depth of the cross-sectional profile reaches 20 μm. The erosion rates of the polyester film in each cycle until the depth of the cross-sectional profile reaches 20 μm are averaged to obtain the E 0-20 Calculate.

[0045] <Calibration> The test liquid is placed in the container. The test liquid in the container is sent to the nozzle. Compressed air is sent into the nozzle to accelerate the test liquid in the nozzle, and an arbitrary amount of the test liquid is sprayed perpendicularly from the nozzle hole at the tip of the nozzle onto an acrylic plate with a thickness of 2 mm, causing the spherical silica in the test liquid to collide with the acrylic plate. The cross-sectional shape of the nozzle is a square of 1 mm x 1 mm, and the distance between the nozzle hole and the acrylic plate is 4 mm. After a given amount of the test liquid is sprayed, the spraying of the test liquid is stopped temporarily. After the spraying of the test liquid is stopped temporarily, a cross-sectional profile is measured at the point on the acrylic plate where the spherical silica in the test liquid collided. The erosion rate (μm / g) of the acrylic plate is calculated by dividing the depth (μm) of the cross-sectional profile by the arbitrary amount (g) mentioned above. The erosion rate of the acrylic plate is set to a pass condition of within ±5% of the standard value of 1.88 (μm / g), and the flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted and calibrated so that the erosion rate of the acrylic plate is within this range.

[0046] The measurement conditions for the erosion rate and the technical significance of the erosion rate calculated under the above measurement conditions will be explained below with reference to Fig. 2. An example of an erosion rate measuring device as shown in Fig. 2 is the MSE test device manufactured by Palmeso Co., Ltd., product number "MSE-A203".

[0047] In the measurement conditions for the erosion rate of the present disclosure, first, a test liquid obtained by mixing pure water, a dispersant, and spherical silica having an average particle size of 4.2 μm within ±8% at a mass ratio of 968:2:30 is placed in a container (11). It is preferable to stir the test liquid in the container (11). The dispersant is not particularly limited as long as it can disperse spherical silica. An example of the dispersant is "Demol N" manufactured by Wako Pure Chemical Industries, Ltd. "The average particle size is within ±8% of 4.2 μm as the standard" means, in other words, that the average particle size is 3.864 μm or more and 4.536 μm or less. In addition, in the measurement conditions of the erosion rate in this specification, the "average particle size of spherical silica" is measured as the volume average value d50 in particle size distribution measurement by laser light diffraction method (the so-called "median size"). In the particle size distribution measurement, the spherical silica preferably has a particle size width with a frequency of 50 within ±10% of 4.2 μm when the frequency of the particle size with the maximum frequency is normalized to 100. The "particle size width with a frequency of 50" is expressed as "XY (μm)" when "X is a particle size with a frequency of 50 and located in the positive direction of the particle size with a frequency of 100" and "Y is a particle size with a frequency of 50 and located in the negative direction of the particle size with a frequency of 100". In this specification, the "particle size width with a frequency of 50" may be referred to as the "full width at half maximum of the particle size distribution".

[0048] An example of spherical silica having an average particle size within ±8% of 4.2 μm is model number "MSE-BS-5-3" specified by Palmeso Co., Ltd. An example of spherical silica corresponding to model number "MSE-BS-5-3" specified by Palmeso Co., Ltd. is product number "BS5-3" of Potters-Ballotini Co., Ltd.

[0049] The test liquid in the container is sent to the nozzle (51). The test liquid can be sent to the nozzle, for example, through a test liquid pipe (21). A flow meter (31) for measuring the flow rate of the test liquid is preferably disposed between the container (11) and the nozzle (51). The flow rate of the test liquid is the value adjusted by the above calibration. In FIG. 2, the nozzle (51) is disposed in a housing (52) that constitutes the ejection part (50).

[0050] Compressed air is fed into the nozzle (51). The compressed air is fed to the nozzle, for example, through a compressed air pipe (22). In the nozzle, the position to which the compressed air is fed is preferably upstream of the position to which the test liquid is fed. The upstream side refers to the side farther from the nozzle injection hole. It is preferable that a flow meter (32) for measuring the flow rate of the compressed air and a pressure meter (42) for measuring the pressure of the compressed air are disposed before the compressed air reaches the nozzle (51). The compressed air can be supplied by an air compressor (not shown) or the like. The flow rate and pressure of the compressed air are adjusted by the above calibration.

[0051] When compressed air is sent into the nozzle (51), the test liquid is accelerated while being mixed by the compressed air. The accelerated test liquid is then sprayed from the nozzle hole at the tip of the nozzle (51) and collides perpendicularly against the polyester film (70). The polyester film is abraded mainly by spherical silica particles in the test liquid. A pressure gauge (41) for measuring the pressure of the test liquid in the nozzle is preferably disposed in the nozzle (51). The pressure gauge (41) is preferably located downstream of the position where the compressed air is fed and the position where the test liquid is fed. The pressure of the test liquid in the nozzle (51) is adjusted by the above calibration.

[0052] The test liquid sprayed from the spray hole at the tip of the nozzle (51) is mixed with air and sprayed in the form of a mist. This makes it possible to reduce the impact pressure of the spherical silica particles against the polyester film. This makes it possible to minimize the amount of abrasion of the polyester film caused by a single spherical silica particle. FIG. 3 is an image of a state in which a polyester film (70) is abraded by a test liquid containing pure water (A1) and spherical silica (A2) sprayed from the spray section (50). In FIG. 3, the symbol A3 indicates air, and the symbol A4 indicates the abraded polyester film. In addition, since the test liquid contains water, which has an excellent cooling effect, deformation and deterioration of the polyester film caused by heat during collision can be substantially eliminated. In other words, abnormal wear of the polyester film can be substantially eliminated. Water also plays a role in cleaning the surface of the worn polyester film and realizing stable wear. Water also plays a role in accelerating the spherical silica particles and controlling the fluid of the test liquid. In addition, since a huge number of spherical silica particles collide with the polyester film, the influence of subtle differences in the physical properties of individual spherical silica particles can be eliminated. Furthermore, the measurement conditions of the present disclosure are the flow rate of the test liquid supplied to the nozzle, the flow rate of the compressed air supplied to the nozzle, the pressure of the compressed air supplied to the nozzle, and the pressure of the test liquid in the nozzle, adjusted by the above calibration, and the cross-sectional shape of the nozzle is specified to be a 1 mm x 1 mm square, and the distance between the injection hole and the polyester film is specified to be 4 mm, thereby specifying the factors that affect the amount of wear of the polyester film. Note that the above distance is the distance indicated by "d" in Figure 2, and means the vertical distance between the injection hole at the tip of the nozzle and the polyester film. From the above, it can be said that the measurement conditions of the present disclosure are measurement conditions that can form statistically stable wear marks on the polyester film.

[0053] The polyester film 70 may be attached to a sample mounting stage 81 of a measuring device 90. The plastic film 70 is preferably attached to the sample mounting stage 81 via a support 82 such as a stainless steel plate.

[0054] The test liquid sprayed onto the polyester film (70) is preferably collected in the receiver (12) and returned to the container (11) through the return pipe (23). A return pump (24) is preferably disposed between the receiver (12) and the return pipe (23).

[0055] The measurement conditions disclosed herein require that after a predetermined amount of test liquid has been sprayed, spraying of the test liquid is stopped temporarily, and that after spraying of the test liquid is stopped temporarily, a cross-sectional profile is measured at the point on the polyester film where the spherical silica in the test liquid collided. The cross-sectional profile refers to the cross-sectional shape of the polyester film abraded by the test liquid. The polyester film is abraded mainly by the spherical silica particles in the test liquid. The cross-sectional profile can be measured by a cross-sectional profile acquisition unit (60) such as a stylus-type surface profile measuring device or a laser interference-type surface profile measuring device. The cross-sectional profile acquisition unit (60) is usually disposed at a position away from the polyester film (70) when the test liquid is sprayed. For this reason, it is preferable that at least one of the polyester film (70) and the cross-sectional profile acquisition unit (60) is movable. The MSE tester model number "MSE-A203" from Palmeso Co., Ltd. uses a stylus to measure cross-sectional profiles.

[0056] Furthermore, under the measurement conditions disclosed herein, one cycle of three steps, namely, a step of spraying a predetermined amount of test liquid from an injection port, a step of temporarily stopping the spraying of the test liquid after spraying the predetermined amount of test liquid, and a step of temporarily stopping the spraying of the test liquid and then measuring the cross-sectional profile, is performed until the depth of the cross-sectional profile exceeds 20 μm. By carrying out the above-mentioned operations, the erosion rate of the polyester film in each cycle can be measured, and further, the variation in the erosion rate of the polyester film can be calculated. The above cycle may be continued even after the depth of the cross-sectional profile exceeds 20 μm, but is preferably terminated when the depth of the cross-sectional profile exceeds 20 μm. The reason for the measurement being "from the surface of the polyester film to a depth of 20 μm" is that the physical properties of the polyester film tend to be more stable toward the inside, while being more variable near the surface.

[0057] In this specification, the erosion rate of each cycle can be calculated by dividing the depth (μm) of the cross-sectional profile progressed in each cycle by the amount (g) of the test liquid sprayed in each cycle. The depth (μm) of the cross-sectional profile of each cycle is the depth of the deepest position of the cross-sectional profile of each cycle.

[0058] In principle, the amount of test liquid sprayed in each cycle is "fixed amount", but some variation in each cycle is acceptable. The amount of test liquid sprayed in each cycle is not particularly limited, but the lower limit is preferably 0.5 g or more, more preferably 1.0 g or more, and the upper limit is preferably 3.0 g or less, more preferably 2.0 g or less.

[0059] Under the measurement conditions of the present disclosure, the erosion rate (μm / g) is calculated for each cycle up to a cross-sectional profile depth of 20 μm. The erosion rates for each cycle up to a cross-sectional profile depth of 20 μm are then averaged to obtain E 0-20 (The average erosion rate from the surface of the polyester film to a depth of 20 μm) is calculated. The above cycles are carried out until the depth of the cross-sectional profile exceeds 20 μm. The data for the cycles in which the depth of the cross-sectional profile exceeds 20 μm is 0-20 This will result in the data being excluded from the calculation.

[0060] In general, the softer the polyester film, the more easily it is scratched, and the harder the polyester film, the less likely it is to be scratched. The present inventors have considered using values ​​(Martens hardness, indentation hardness, elastic recovery work load, etc.) obtained by evaluation including the depth direction using a picodenter as an index of pencil hardness. However, there were cases where the above-mentioned parameters such as Martens hardness, indentation hardness, and elastic recovery work load could not be used as an index of pencil hardness. In addition, the strength of polyester films tends to increase when they are stretched. Specifically, uniaxially stretched polyester films tend to have a better pencil hardness than unstretched polyester films, and biaxially stretched polyester films tend to have a better pencil hardness than uniaxially stretched polyester films. However, even biaxially stretched polyester films sometimes have insufficient pencil hardness. The present inventors have investigated the erosion rate as an index of the pencil hardness of polyester films. As described above, a softer polyester film is more susceptible to damage, and a harder polyester film is less susceptible to damage. Therefore, it is thought that a smaller erosion rate would lead to a better pencil hardness. However, the present inventors have found that the erosion rate (E 0-20 The inventors have found that by increasing the erosion ratio to 1.4 μm / g or more, the polyester film can have a good pencil hardness. The inventors have also found that the erosion ratio of a polyester film is likely to be higher in a biaxially oriented polyester film than in a uniaxially oriented polyester film, and that the pencil hardness of a biaxially oriented polyester film can be determined by the erosion ratio.

[0061] The reason why the erosion rate of the polyester film correlates with the pencil hardness is believed to be as follows. As described above, under the measurement conditions of the present disclosure, the test liquid containing water and spherical silica is mixed with air and sprayed in the form of mist.Therefore, the impact pressure of spherical silica particles against polyester film is suppressed to be low.Therefore, when the polyester film is soft, the stress when spherical silica collides with the polyester film is easily dispersed, so the polyester film is less likely to be worn, and the erosion rate is considered to be low.On the other hand, when the polyester film is hard, the stress when spherical silica collides with the polyester film is not easily dispersed, so the polyester film is easily worn, and the erosion rate is considered to be high. In addition, the difference in the erosion rate in the biaxially stretched polyester film is considered to be caused by the difference in the degree of stretching of the molecular chain and the difference in the degree of molecular orientation. For example, in the biaxially stretched polyester film, the molecules are stretched in the plane in principle, but there may be molecules that are not sufficiently stretched locally in the plane. In this way, when the proportion of molecules that are not sufficiently stretched locally in the plane increases, the biaxially stretched polyester film is considered to become locally soft and the erosion rate is considered to decrease. In addition, even if the biaxially stretched polyester film has the same in-plane retardation, it is considered to show different erosion rates due to the difference in the local molecular orientation.

[0062] In order to improve the pencil hardness of the polyester film, E 0-20 is preferably 1.4 μm / g or more, more preferably 1.5 μm / g or more, more preferably 1.6 μm / g or more, more preferably 1.78 μm / g or more, more preferably 1.8 μm / g or more, more preferably 1.9 μm / g or more, and more preferably 2.0 μm / g or more. E 0-20 In order to make the polyester film less likely to crack, the hardness is preferably 3.0 μm / g or less, more preferably 2.5 μm / g or less, even more preferably 2.2 μm / g or less, and still more preferably 2.07 μm / g or less.

[0063] Polyester film E 0-20Preferred embodiments of the range are 1.4 μm / g or more and 3.0 μm / g or less, 1.4 μm / g or more and 2.5 μm / g or less, 1.4 μm / g or more and 2.2 μm / g or less, 1.4 μm / g or more and 2.07 μm / g or less, 1.5 μm / g or more and 3.0 μm / g or less, 1.5 μm / g or more and 2.5 μm / g or less, 1.5 μm / g or more and 2.2 μm / g or less, 1.5 μm / g or more and 2.07 μm / g or less, 1.6 μm / g or more and 3.0 μm / g or less, 1.6 μm / g or more and 2.5 μm / g or less. Examples of the saturation index include 1.6 μm / g or more and 2.2 μm / g or less, 1.6 μm / g or more and 2.07 μm / g or less, 1.78 μm / g or more and 3.0 μm / g or less, 1.78 μm / g or more and 2.5 μm / g or less, 1.78 μm / g or more and 2.2 μm / g or less, 1.78 μm / g or more and 2.07 μm / g or less, 1.8 μm / g or more and 3.0 μm / g or less, 1.8 μm / g or more and 2.5 μm / g or less, 1.8 μm / g or more and 2.2 μm / g or less, and 1.8 μm / g or more and 2.07 μm / g or less.

[0064] Before measuring the above-mentioned erosion rate, the above-mentioned calibration is carried out. The calibration can be performed as follows:

[0065] <Calibration> The test liquid is placed in the container. The test liquid in the container is sent to the nozzle. Compressed air is sent into the nozzle to accelerate the test liquid in the nozzle, and an arbitrary amount of the test liquid is sprayed perpendicularly from the nozzle hole at the tip of the nozzle onto an acrylic plate with a thickness of 2 mm, causing the spherical silica in the test liquid to collide with the acrylic plate. The cross-sectional shape of the nozzle is a square of 1 mm x 1 mm, and the distance between the nozzle hole and the acrylic plate is 4 mm. After a given amount of the test liquid is sprayed, the spraying of the test liquid is stopped temporarily. After the spraying of the test liquid is stopped temporarily, a cross-sectional profile is measured at the point on the acrylic plate where the spherical silica in the test liquid collided. The erosion rate (μm / g) of the acrylic plate is calculated by dividing the depth (μm) of the cross-sectional profile by the arbitrary amount (g) mentioned above. The erosion rate of the acrylic plate is set to a pass condition of within ±5% of the standard value of 1.88 (μm / g), and the flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted and calibrated so that the erosion rate of the acrylic plate is within this range.

[0066] The test liquid used for calibration shall be the same as the test liquid used under the measurement conditions to be carried out later. The measurement device used in the calibration is the same as the measurement device used under the measurement conditions to be carried out later. The difference between the calibration and the measurement conditions to be carried out later is, for example, that the calibration uses a 2 mm thick acrylic plate as a standard sample, whereas the measurement conditions use a polyester film as the sample.

[0067] The 2 mm thick acrylic plate serving as the standard sample is preferably a polymethyl methacrylate plate (PMMA plate). In addition, when the average erosion rate of the acrylic plate measured under the following measurement condition A is defined as AcE, the 2 mm thick acrylic plate serving as the standard sample is preferably one having an AcE of 1.786 μm / g or more and 1.974 μm / g or less. In addition, an example of the spherical silica under the following measurement condition A is the model number "MSE-BS-5-3" specified by Palmeso Co., Ltd. An example of the spherical silica corresponding to the model number "MSE-BS-5-3" specified by Palmeso Co., Ltd. is the product number "BS5-3" of Potters-Ballotini Co., Ltd. <Measurement condition A> A test liquid obtained by mixing pure water, a dispersant, and spherical silica with an average particle size of 4.2 μm within ±8% at a mass ratio of 968:2:30 is placed in a container. The test liquid in the container is sent to a nozzle. Compressed air is sent into the nozzle to accelerate the test liquid in the nozzle, and a predetermined amount of the test liquid is sprayed perpendicularly to the acrylic plate from the injection hole at the tip of the nozzle, causing the spherical silica in the test liquid to collide with the acrylic plate. The cross-sectional shape of the nozzle is a square of 1 mm x 1 mm, and the distance between the injection hole and the acrylic plate is 4 mm. In addition, the flow rates of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are as follows: flow rate of test liquid is 100 ml / min or more and 150 ml / min or less, flow rate of compressed air is 4.96 L / min or more and 7.44 L / min or less, pressure of compressed air is 0.184 MPa or more and 0.277 MPa or less, and pressure of test liquid in the nozzle is 0.169 MPa or more and 0.254 MPa or less. After 4 g of the test liquid was sprayed, the spraying of the test liquid was temporarily stopped. After the spraying of the test liquid is temporarily stopped, a cross-sectional profile is measured at the point on the acrylic plate where the spherical silica in the test liquid collided. Then, the erosion rate of the acrylic plate, AcE (unit: μm / g), is calculated by dividing the depth (μm) of the cross-sectional profile by the amount of the test liquid sprayed (4 g).

[0068] In the calibration, the erosion rate of the acrylic plate is set to be within a range of ±5% of the standard value of 1.88 (μm / g), and the flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted so that the erosion rate of the acrylic plate is within this range. In addition, "the erosion rate is ±5% with 1.88 (μm / g) as the standard" means, in other words, that the erosion rate is 1.786 (μm / g) or more and 1.974 (μm / g) or less.

[0069] <σ 0-20 / E 0-20 > The polyester film is calculated from the erosion rate from the surface of the polyester film to a depth of 20 μm, and the variation in the erosion rate is σ 0-20 When we define 0-20 / E 0-20 It is preferable that the ratio is 0.100 or less. In this specification, σ 0-20 can be calculated from the erosion rate of each cycle up to a depth of 20 μm in the cross-sectional profile under the above measurement conditions.

[0070] σ 0-20 / E 0-20 indicates the coefficient of variation of the erosion rate, and σ 0-20 / E 0-20 A small value of σ means that the erosion rate is unlikely to vary in the thickness direction of the polyester film. 0-20 / E 0-20 By making the ratio 0.100 or less, the erosion rate in the thickness direction is stabilized, and it is easier to obtain a good pencil hardness.

[0071] σ 0-20 / E 0-20 The upper limit of is more preferably 0.080 or less, further preferably 0.077 or less, further preferably 0.070 or less, further preferably 0.060 or less, and further preferably 0.055 or less. σ 0-20 / E 0-20 The lower limit of is not particularly limited, but is usually 0.020 or more, preferably 0.035 or more, and more preferably 0.040 or more. 0-20 / E 0-20 When the value of σ is low, the polyester film may be weakly stretched. A polyester film with a low stretching ratio tends to have poor solvent resistance, be easily broken, and have low stability against heat and humidity. 0-20 / E 0-20 is preferably 0.020 or more.

[0072] σ 0-20 / E 0-20Preferred embodiments of the range include 0.020 or more and 0.100 or less, 0.020 or more and 0.080 or less, 0.020 or more and 0.077 or less, 0.020 or more and 0.070 or less, 0.020 or more and 0.060 or less, 0.020 or more and 0.055 or less, 0.035 or more and 0.100 or less, 0.035 or more and 0.080 or less, 0.035 or more and 0.077 or less, 0.035 or more and 0.070 or less, 0.035 or more and 0.060 or less, 0.035 or more and 0.055 or less, 0.040 or more and 0.100 or less, 0.040 or more and 0.080 or less, 0.040 or more and 0.077 or less, 0.040 or more and 0.070 or less, 0.040 or more and 0.060 or less, and 0.040 or more and 0.055 or less.

[0073] -Thickness- In order to improve the mechanical strength, the thickness of the polyester film is preferably 10 μm or more, more preferably 21 μm or more, even more preferably 25 μm or more, and even more preferably 30 μm or more. In addition, by making the thickness of the polyester film 10 μm or more, when another member contacts the side opposite to the functional layer of the optical laminate and stress is generated, the stress can be prevented from being transmitted to the interface between the polyester film and the easy-adhesion layer. In order to reduce the in-plane retardation and improve the bending resistance, the thickness of the polyester film is preferably 75 μm or less, more preferably 60 μm or less, even more preferably 55 μm or less, and even more preferably 50 μm or less.

[0074] Preferred embodiments of the thickness range of the polyester film include 10 μm or more and 75 μm or less, 10 μm or more and 60 μm or less, 10 μm or more and 55 μm or less, 10 μm or more and 50 μm or less, 21 μm or more and 75 μm or less, 21 μm or more and 60 μm or less, 21 μm or more and 55 μm or less, 21 μm or more and 50 μm or less, 25 μm or more and 75 μm or less, 25 μm or more and 60 μm or less, 25 μm or more and 55 μm or less, 25 μm or more and 50 μm or less, 30 μm or more and 75 μm or less, 30 μm or more and 60 μm or less, 30 μm or more and 55 μm or less, and 30 μm or more and 50 μm or less.

[0075] 《Raw materials》 Examples of polyesters that make up the polyester film include homopolymers obtained by polycondensation of dicarboxylic acids and diols; copolymers obtained by polycondensation of one or more dicarboxylic acids and two or more diols; copolymers obtained by polycondensation of two or more dicarboxylic acids and one or more diols; and blend resins that are a mixture of one or more homopolymers and one or more copolymers. The polyester film may contain additives such as ultraviolet absorbers, easily slippery particles such as inorganic particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, antistatic agents, light resistance agents, flame retardants, heat stabilizers, antioxidants, antigelling agents, and surfactants, as long as the effects of the present disclosure are not impaired. The raw materials for the polyester film may be newly synthesized, naturally occurring, or recycled.

[0076] Examples of dicarboxylic acids include terephthalic acid, isophthalic acid, orthophthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenediyl carboxylic acid, diphenyl carboxylic acid, diphenoxyethane dicarboxylic acid, diphenylsulfone carboxylic acid, anthracene dicarboxylic acid, 1,3-cyclopentane dicarboxylic acid, 1,3-cyclohexane dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, and dodecane dicarboxylic acid. Diols include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadiol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.

[0077] Among polyesters, polyethylene terephthalate is preferred in order to improve mechanical strength, that is, the polyester film preferably contains polyethylene terephthalate.

[0078] Polymerization methods for polyethylene terephthalate include a direct polymerization method in which terephthalic acid is directly reacted with ethylene glycol, and if necessary, other dicarboxylic acid components and diol components; an ester exchange method in which a dimethyl ester of terephthalic acid is subjected to an ester exchange reaction with ethylene glycol; and the like. In the ester exchange method, the dimethyl ester of terephthalic acid may contain a methyl ester of another dicarboxylic acid if necessary. In the ester exchange method, the ethylene glycol may contain another diol component if necessary.

[0079] The intrinsic viscosity of the polyethylene terephthalate is preferably 0.45 or more and 0.70 or less. If the intrinsic viscosity is lower than 0.45, the tear resistance may decrease. If the intrinsic viscosity is higher than 0.70, the filtration pressure increases significantly, which may decrease the filtration accuracy.

[0080] 《Layer composition》 The polyester film may be of a single layer or multilayer structure. The single-layer structure makes it easy to control the stretching. Therefore, the single-layer structure makes it easy to increase the pencil hardness of the polyester film without lowering the stretching ratio in the machine direction and the width direction, and by making the stretching ratios in both directions close to each other. Therefore, the single-layer structure, which makes it easy to control the stretching, is preferable in that it makes it easy to increase the pencil hardness of the polyester film. In addition, in order to control the erosion rate, it is important to stretch the molecules evenly within the plane of the polyester film. Therefore, the single-layer structure is preferable in that it makes it easy to control the erosion rate. On the other hand, a multi-layer polyester film is preferable because it is easy to impart effects by changing the composition of each layer. For example, if a laminated polyester film consisting of at least three layers is produced by coextrusion and a polyester with a low oligomer content is used for the surface layers on both sides, it is easy to suppress the amount of oligomer precipitation after heat treatment.

[0081] -Stretching- In order to increase the pencil hardness of the polyester film, it is preferable to make the stretching ratios in the machine direction and the width direction close to each other without decreasing them. For this reason, the polyester film is preferably a stretched film, more preferably a biaxially stretched film.

[0082] -Sequential biaxial stretching- In sequential biaxial stretching, the casting film is stretched in the machine direction, and then stretched in the width direction of the film. The stretching in the machine direction is usually performed by the difference in peripheral speed between a pair of stretching rolls. The stretching in the machine direction may be performed in one stage, or may be performed in multiple stages using a plurality of pairs of stretching rolls. In order to suppress excessive variation in optical properties such as in-plane retardation, it is preferable to place a plurality of nip rolls close to the stretching roll. The stretching ratio in the machine direction is usually 2 to 15 times, and in order to suppress excessive variation in optical properties such as in-plane retardation, it is preferably 2 to 7 times, more preferably 3 to 5 times, and even more preferably 3 to 4 times. In order to suppress excessive variation in physical properties such as in-plane retardation, the stretching temperature is preferably from the glass transition temperature of the resin to the glass transition temperature + 100° C. In the case of PET, the temperature is preferably from 70° C. to 120° C., more preferably from 80° C. to 110° C., and even more preferably from 95° C. to 110° C. Regarding the stretching temperature, the average in-plane retardation tends to be small by shortening the stretching section at low temperature by heating the film quickly, whereas the average in-plane retardation tends to be large by increasing the stretching section at low temperature by heating the film slowly. In addition, in the case of stretching in the machine direction, the erosion rate tends to decrease when the stretching time is shortened, and to increase when the stretching time is lengthened. This is thought to be because, when the stretching time is short, the molecules are not easily stretched evenly in the plane of the polyester film, whereas, when the stretching time is long, the molecules are easily stretched evenly in the plane of the polyester film. That is, E 0-20 In order to make the stretching time 1.4 μm / g or more, it is preferable to extend the stretching time. Furthermore, by lengthening the stretching time while appropriately increasing the stretching ratio so that the physical properties do not vary, it is possible to further increase the E 0-20 It is possible to easily achieve a particle size of 1.4 μm / g or more.

[0083] A layer having functions such as easy lubrication and antistatic properties may be formed on the film stretched in the machine direction by in-line coating or off-line coating. In this specification, the layer formed by in-line coating or off-line coating is not counted as the number of layers constituting the polyester film.

[0084] The stretching in the width direction is usually performed by conveying the film while holding both ends with clips using a tenter method, and stretching the film in the width direction. The stretching ratio in the width direction is usually 2 to 15 times, and is preferably 2 to 7 times, more preferably 3 to 6 times, and even more preferably 4 to 5 times, in order to suppress excessive variation in physical properties such as in-plane retardation. It is also preferable to make the stretching ratio in the width direction higher than the stretching ratio in the machine direction. The stretching temperature is preferably from the glass transition temperature of the resin to the glass transition temperature + 120°C, and the temperature preferably increases from the upstream to the downstream. Specifically, when the widthwise stretching section is divided into two, the difference between the upstream and downstream temperatures is preferably 20°C or more, more preferably 30°C or more, even more preferably 35°C or more, and even more preferably 40°C or more. In the case of PET, the first-stage stretching temperature is preferably 80°C to 120°C, more preferably 90°C to 110°C, and even more preferably 95°C to 105°C.

[0085] The polyester film sequentially biaxially stretched as described above is preferably heat-treated in a tenter at a temperature equal to or higher than the stretching temperature and lower than the melting point in order to impart planarity and dimensional stability. Specifically, in the case of PET, heat setting is preferably performed in the range of 150°C to 255°C, more preferably 200°C to 250°C. In addition, in order to suppress excessive variation in physical properties such as in-plane retardation, it is preferable to perform additional stretching of 1% to 10% in the first half of the heat treatment. After the polyester film is heat-treated, it is slowly cooled to room temperature and then wound up. If necessary, a relaxation treatment or the like may be used in combination with the heat treatment or the slow cooling. The relaxation rate during the heat treatment is preferably 0.5% to 5% in order to suppress excessive variation in physical properties such as in-plane retardation, more preferably 0.5% to 3% in order to suppress excessive variation in physical properties such as in-plane retardation, and is more preferably 0.8% to 2.5% in order to suppress excessive variation in physical properties such as in-plane retardation, and is more preferably 1% to 2% in order to suppress excessive variation in physical properties such as in-plane retardation, and is more preferably 0.5% to 3% in order to suppress excessive variation in physical properties such as in-plane retardation, and is more preferably 0.5% to 2% in order to suppress excessive variation in physical properties such as in-plane retardation, and is more preferably 0.5% to 1.0% in order to suppress excessive variation in physical properties such as in-plane retardation. In order to facilitate good flatness, the temperature during slow cooling is preferably 80°C or higher and 150°C or lower, more preferably 90°C or higher and 130°C or lower, even more preferably 100°C or higher and 130°C or lower, and even more preferably 100°C or higher and 120°C or lower.

[0086] The conveying speed during production of the stretched polyester film is generally about 100 m / s or more and 300 m / s or less.

[0087] -Simultaneous biaxial stretching- In the simultaneous biaxial stretching, the casting film is introduced into a simultaneous biaxial tenter, and the film is conveyed while both ends are held by clips, and stretched simultaneously and / or stepwise in the machine direction and width direction. The simultaneous biaxial stretching machine may be of the pantograph type, screw type, drive motor type, or linear motor type, but the drive motor type or linear motor type is preferred because it can change the stretch ratio at any time and can perform relaxation treatment at any location.

[0088] The area ratio of the simultaneous biaxial stretching is usually 6 to 50 times. In order to suppress excessive variation in physical properties such as in-plane retardation, the area ratio is preferably 8 to 30 times, more preferably 9 to 25 times, even more preferably 9 to 20 times, and still more preferably 10 to 15 times. In the simultaneous biaxial stretching, the stretch ratio in the machine direction and the stretch ratio in the width direction are preferably adjusted to the above area ratio within the range of 2 to 15 times. In the case of simultaneous biaxial stretching, in order to suppress in-plane orientation differences, it is preferable to make the stretching ratios in the machine direction and the width direction approximately the same, and to make the stretching speeds in the machine direction and the width direction approximately the same.

[0089] In order to suppress excessive variation in physical properties such as in-plane retardation, the stretching temperature in simultaneous biaxial stretching is preferably from the glass transition temperature of the resin to the glass transition temperature + 120° C. In the case of PET, the stretching temperature is preferably from 80° C. to 160° C., more preferably from 90° C. to 150° C., and even more preferably from 100° C. to 140° C.

[0090] The simultaneously biaxially stretched film is preferably subsequently subjected to a heat treatment at a temperature equal to or higher than the stretching temperature and lower than the melting point in a heat fixing chamber in a tenter in order to impart flatness and dimensional stability. The heat treatment conditions are the same as those after the successive biaxial stretching.

[0091] <Easy adhesion layer> The polyester film with an easy-adhesion layer of the present disclosure is required to have an easy-adhesion layer. Also, the polyester film with an easy-adhesion layer of the present disclosure is required to have an average value of δq / δa of the surface of the easy-adhesion layer of 1.60 or less.

[0092] -Calculation of the average value of δq / δa- A 10 μm×10 μm area on the surface of the easy-adhesion layer is measured in phase mode with an atomic force microscope. The measurement results in a distribution of phase signals on the surface of the easy-adhesion layer. The unit of the phase signal is [deg]. The arithmetic mean value of the phase signal shown in the following formula 1 is denoted as δa, and the root mean square value of the phase signal shown in the following formula 2 is denoted as δq. (In the following formulas 1 and 2, the orthogonal coordinate axes X and Y are placed on a reference surface indicating the average value of the phase signal, the axis perpendicular to the reference surface is the Z axis, and the curved surface of the phase signal is f(x, y). In the following formulas 1 and 2, the sizes of the regions for calculating δa and δq are Lx and Ly. In the following formulas 1 and 2, Ar=Lx×Ly.) Seven measurement evaluation areas of 2 μm × 2 μm are selected from the measurement area of ​​10 μm × 10 μm. Calculate δa, δq, and δq / δa for each of the seven measurement evaluation areas. Calculate the average value of δq / δa based on the five δq / δa values ​​excluding the maximum and minimum values ​​from the seven δq / δa values. The seven measurement evaluation regions may partially overlap each other, provided that the overlapping ratio between any one of the measurement evaluation regions and the other six measurement evaluation regions is preferably 25% or less, more preferably 12% or less, and even more preferably 5% or less, based on the area of ​​the measurement evaluation regions.

[0093]

number

[0094]

number

[0095] When the polyester film does not have an easy-adhesion layer, even if a functional layer is formed on the polyester film, the adhesion of the optical laminate having the polyester film and the functional layer cannot be made good. Furthermore, even if an easy-adhesion layer is formed on a polyester film, if the average value of δq / δa of the surface of the easy-adhesion layer exceeds 1.60, the adhesion of an optical laminate having a polyester film, an easy-adhesion layer, and a functional layer in that order cannot be improved.

[0096] The technical significance of the average value of δq / δa on the surface of the adhesive layer will be described below. δa and δq are parameters related to the phase signal when a predetermined area on the surface of the easy-adhesion layer is measured in the phase mode of an atomic force microscope. The unit of the phase signal is [deg]. The phase signal indicates the viscoelasticity of the surface of the easy-adhesion layer. An atomic force microscope is a device that measures the physical properties of a surface by scanning the surface of a sample with a minute probe attached to a leaf spring. In the phase mode, the probe is vibrated while measuring, so that the change in the vibration phase in the plane can be mapped. Therefore, in the phase mode, the contrast caused by the difference in viscoelasticity of the surface components can be mapped. δa is the arithmetic mean value of the phase signal in a predetermined region. On the other hand, δq is the root mean square value of the phase signal in a predetermined region. The root mean square value emphasizes values ​​far from the arithmetic mean value. Therefore, even if the value of δa, which is the arithmetic mean value, is the same, if the variation in the phase signal in a predetermined region is large, the average value of δq, which is the root mean square value, becomes large. Similarly, even if the value of δa, which is the arithmetic mean value, is the same, if the variation in the phase signal in a predetermined region is large, the average value of δq / δa becomes large. Conversely, even if the value of δa, which is the arithmetic mean value, is the same, if the variation in the phase signal in a predetermined region is small, the average value of δq / δa becomes small. That is, an easy-adhesion layer with a small arithmetic mean value of δq / δa indicates that the phase signal is concentrated in the vicinity of the arithmetic mean value of the phase signal in a predetermined region, and the variation in the phase signal in the predetermined region is small. Since the phase signal indicates the viscoelasticity of the surface of the easy-adhesion layer, an easy-adhesion layer with a small average value of δq / δa indicates that the change in viscoelasticity is small in the predetermined region. In addition, the phase signal indicates the relative change amount within the same image. Therefore, generally, δa and δq of different samples cannot be compared. In the present disclosure, attention is paid to δq / δa, which is the ratio of δa to δq. As described above, δq / δa is a parameter indicating the phase variation within a sample, and is a dimensionless parameter. Therefore, δq / δa can be said to be appropriate as a parameter for comparing the phase variation between samples.

[0097] As described above, an easy-adhesion layer having a small average value of δq / δa shows a small change in viscoelasticity in a specified region. And, a polyester film having an easy-adhesion layer having a small average value of δq / δa can improve the adhesion of an optical laminate having a functional layer formed on the easy-adhesion layer. The adhesion of the optical laminate is considered to be improved for the following reasons. When another member comes into contact with the functional layer of the optical laminate, a certain stress is generated. The stress is transmitted to the interface between the polyester film and the easy-adhesion layer through the functional layer and the easy-adhesion layer. The way in which the stress is transmitted depends on the value of the viscoelasticity of the easy-adhesion layer. Therefore, when the change in the viscoelasticity in the plane of the easy-adhesion layer is large, the magnitude of the stress transmitted to the interface between the polyester film and the easy-adhesion layer will differ depending on the location in the plane. Therefore, when the average value of δq / δa of the easy-adhesion layer is large, a large stress is likely to be applied to a certain location in the plane, and the interfacial peeling of the optical laminate is likely to occur. On the other hand, when the average value of δq / δa of the easy-adhesion layer is small, the stress is dispersed in the plane, so that it is considered that the interfacial peeling of the optical laminate can be suppressed and the adhesion can be improved. The reason why the viscoelasticity of the adhesive layer varies from place to place is thought to be due to the compatibility of the components constituting the adhesive layer, etc.

[0098] The average value of Δq / Δa is preferably 1.57 or less, more preferably 1.54 or less, more preferably 1.536 or less, more preferably 1.50 or less, more preferably 1.45 or less, and more preferably 1.40 or less. The smaller the average value of δq / δa, the more homogeneous the viscoelasticity of the surface of the easy-adhesion layer becomes. If the viscoelasticity of the surface of the easy-adhesion layer is too homogeneous, the components of the functional layer may not penetrate the easy-adhesion layer easily, and the adhesion between the easy-adhesion layer and the functional layer may not be improved. For this reason, the average value of δq / δa is preferably 1.125 or more, more preferably 1.20 or more, more preferably 1.25 or more, more preferably 1.30 or more, and more preferably 1.326 or more.

[0099] Preferred embodiments of the average value of δq / δa are 1.125 to 1.60, 1.125 to 1.57, 1.125 to 1.54, 1.125 to 1.536, 1.125 to 1.50, 1.125 to 1.45, 1.125 to 1.40, 1.20 to 1.60, 1.20 to 1.57, 1.20 to 1.54, 1.20 to 1.536, 1.20 to 1.50, 1.20 to 1.45, 1.20 to 1.40, 1.25 to 1.60, 1.25 to 1.57, 1.25 to 1.54 1.25 or more and 1.536 or less, 1.25 or more and 1.50 or less, 1.25 or more and 1.45 or less, 1.25 or more and 1.40 or less, 1.30 or more and 1.60 or less, 1.30 or more and 1.57 or less, 1.30 or more and 1.54 or less, 1.30 or more and 1.536 or less, 1.30 or more and 1.50 or less, 1.30 or more and 1.45 or less, 1.30 or more and 1.40 or less, 1.326 or more and 1.60 or less, 1.326 or more and 1.57 or less, 1.326 or more and 1.54 or less, 1.326 or more and 1.536 or less, 1.326 or more and 1.50 or less, 1.326 or more and 1.45 or less, and 1.326 or more and 1.40 or less.

[0100] The average value of δq / δa on the surface of the easy-adhesion layer is a value in a predetermined region of 10 μm×10 μm. Of the total surface area of ​​the easy-adhesion layer, the proportion of the area in which the average value of δq / δa is 1.60 or less is preferably 80% or more, more preferably 90% or more, even more preferably 95% or more, even more preferably 98% or more, and most preferably 100%.

[0101] When the polyester film with an easy-adhesion layer is in the form of a sheet, among the 10 10 μm×10 μm regions specified in the following (1) to (4), the number of locations where the average value of δq / δa is 1.60 or less is preferably 8 or more, more preferably 9 or more, and even more preferably 10. Among the 10 locations, the number of locations where the coefficient of variation of δq / δa is 0.040 or less is preferably 8 or more, more preferably 9 or more, and even more preferably 10. (1) Draw a circumscribing circle B1 that circumscribes sheet S. (2) Draw an inscribed circle B2 inscribed in the sheet, centered on the center of the circumscribed circle B1. (3) Draw a circle B3 whose diameter is half the diameter of the inscribed circle B2, centered on the center of the circumscribed circle B1. (4) Ten 10 μm×10 μm regions are selected at equal intervals on the circumference of the circle B3. Reference characters C1 and C6 in FIG. 4 correspond to some of the 10 10 μm×10 μm regions.

[0102] When the polyester film with an easy-adhesion layer is in the form of a roll, a sheet is cut out from the roll, and the average value of δq / δa and the coefficient of variation of δq / δa are measured for the cut-out sheet. In addition, of the 10 10 μm×10 μm regions specified in (1) to (4) above, the number of locations where the average value of δq / δa is 1.60 or less is preferably 8 or more, more preferably 9 or more, and even more preferably 10. In addition, of the 10 locations, the number of locations where the coefficient of variation of δq / δa is 0.040 or less is preferably 8 or more, more preferably 9 or more, and even more preferably 10. The physical properties of the polyester film with an easy-adhesion layer in the roll form are generally consistent in the flow direction. Therefore, when a sheet cut from an arbitrary position A in the width direction satisfies the average value of δq / δa of the present disclosure, it can be assumed that the average value is satisfied in the entire flow direction of the roll at the arbitrary position A. The same can be said about the coefficient of variation of δq / δa. To be sure, a sheet may be cut from two places, the core side of the roll and the surface side of the roll, at the arbitrary position A, and the cut-out sheets may be measured. In the case of the core side of the roll, it is preferable to sample from a place away from the core. This is because the place close to the core may have defects such as a winding habit. When the thickness of the polyester film is 40 μm or more, the place away from the core is preferably 10 m or more and 20 m or less from the core, and when the thickness of the polyester film is less than 40 μm, it is preferable to sample from the core more than 20 m and 40 m or less from the core. The rolled polyester film with an easy-adhesion layer may have varying physical properties in the width direction, and therefore it is preferable to divide the roll into 5 equal parts in the width direction, cut out sheets from each of the 5 equal parts, and measure the average value of Δq / Δa for the cut out sheets.

[0103] In the present disclosure, δa can be calculated by the above formula 1. Formula 1 uses the formula for arithmetic mean height in ISO 25178-2:2012. In other words, the formula for arithmetic mean height in ISO 25178-2:2012 uses altitude as data for the Z axis, but formula 1 uses a phase signal [deg], not altitude, as data for the Z axis. That is, δa and the arithmetic mean height in ISO 25178-2:2012 are different in that the former uses a phase signal [deg] as data for the Z axis, whereas the latter uses altitude [μm] as data for the Z axis. In the present disclosure, δq can be calculated by the above formula 2. Formula 2 uses the formula for the root mean square height of ISO 25178-2:2012. In other words, the formula for the root mean square height of ISO 25178-2:2012 uses altitude as data for the Z axis, but Formula 2 uses a phase signal [deg], not altitude, as data for the Z axis. That is, δq and the root mean square height of ISO 25178-2:2012 are different in that the former uses a phase signal [deg] as data for the Z axis, while the latter uses altitude [μm] as data for the Z axis.

[0104] The average value of Δq / Δa can be calculated by the following steps A1 to A4. (A1) A 10 μm×10 μm area on the surface of the easy-adhesion layer is measured in phase mode with an atomic force microscope. (When measuring using Shimadzu Corporation's product name "SPM-9600", it is preferable to adjust the P gain, I gain, and offset.) (A2) Seven measurement evaluation areas of 2 μm × 2 μm are selected from within the measurement area of ​​10 μm × 10 μm. (A3) Calculate δa, δq and δq / δa within the seven selected measurement and evaluation areas. (A4) The maximum and minimum values ​​of δq / δa at seven locations are excluded, and the average value of δq / δa at five locations is calculated.

[0105] In the above A1, an example of the atomic force microscope is Shimadzu Corporation's product name "SPM-9600".

[0106] In the above A2, the 2 μm×2 μm region is selected from a region where the maximum height of the amplitude measured by an atomic force microscope is 90 nm or less. The maximum height is the maximum height Sz of ISO 25178-2:2012. By selecting the 2 μm×2 μm region from a region where Sz is 90 nm or less, the influence of foreign matter and defects can be easily eliminated. It is preferable that the seven measurement evaluation regions are selected so that they do not overlap with each other, but they may overlap with each other. In addition, when the measurement evaluation regions overlap, the overlap rate between any measurement evaluation region and the other six measurement evaluation regions is preferably 25% or less, more preferably 12% or less, and even more preferably 5% or less, based on the area of ​​the measurement evaluation region. In addition, in the above A2, the measurement evaluation area of ​​2 μm×2 μm is preferably selected from an area in which the arithmetic mean height of the amplitude measured by an atomic force microscope is 10 nm or less in order to more easily eliminate the influence of foreign matter and defects. The arithmetic mean height is the arithmetic mean height Sa of ISO 25178-2:2012.

[0107] The easy-adhesion layer preferably has a coefficient of variation of Δq / Δa calculated based on Δq / Δa at the five points of 0.040 or less. By setting the coefficient of variation of δq / δa to 0.040 or less, stress is more easily dispersed within the plane, and adhesion can be more easily improved. The coefficient of variation of δq / δa is more preferably 0.039 or less, more preferably 0.037 or less, and even more preferably 0.035 or less. If the coefficient of variation of δq / δa is too small, the components of the functional layer may not easily penetrate into the adhesive layer, and the adhesion between the adhesive layer and the functional layer may not be improved. Therefore, the coefficient of variation of δq / δa is preferably 0.009 or more, more preferably 0.010 or more, more preferably 0.015 or more, and more preferably 0.018 or more.

[0108] Preferred embodiments of the range of δq / δa include 0.009 or more and 0.040 or less, 0.009 or more and 0.039 or less, 0.009 or more and 0.037 or less, 0.009 or more and 0.035 or less, 0.010 or more and 0.040 or less, 0.010 or more and 0.039 or less, 0.010 or more and 0.037 or less, 0.010 or more and 0.035 or less, 0.015 or more and 0.040 or less, 0.015 or more and 0.039 or less, 0.015 or more and 0.037 or less, 0.015 or more and 0.035 or less, 0.018 or more and 0.040 or less, 0.018 or more and 0.039 or less, 0.018 or more and 0.037 or less, and 0.018 or more and 0.035 or less.

[0109] Of the total surface area of ​​the easy-adhesion layer, the proportion of the area in which the coefficient of variation of δq / δa is 0.040 or less is preferably 80% or more, more preferably 90% or more, even more preferably 95% or more, even more preferably 98% or more, and most preferably 100%.

[0110] The resin constituting the easy-adhesion layer is not particularly limited, and examples thereof include thermoplastic resins and thermosetting resins such as polyester resins, polyurethane resins, and acrylic resins, and thermoplastic resins are preferred. Among the thermoplastic resins, polyester resins and polyurethane resins that can easily reduce the refractive index difference between the polyester film and the easy-adhesion layer, and the refractive index difference between the easy-adhesion layer and the uneven layer are preferred, and resins that contain both polyester and polyurethane components are more preferred. The polyurethane component tends to improve adhesion but does not improve coating strength. For this reason, it is preferable to include both the polyester component and the polyurethane component. However, if the polyurethane component is too much compared to the polyester component, phase separation is likely to occur, so the average value of δq / δa and the coefficient of variation of δq / δa tend to increase. In addition, since the polyurethane component is soft, if the polyurethane component is too much, the average value of δq / δa and the coefficient of variation of δq / δa tend to increase due to differences in in-plane crosslink density. For this reason, in a resin containing both the polyester component and the polyurethane component, the polyester component and the polyurethane component are preferably in a mass ratio of 95:5 to 60:40, more preferably 90:10 to 60:40.

[0111] The resin constituting the easy-adhesion layer preferably has a number-average molecular weight of 10,000 or more, more preferably 15,000 or more. The resin preferably has a number-average molecular weight of 100,000 or less, more preferably 60,000 or less. By setting the number-average molecular weight of the resin constituting the easy-adhesion layer within the above range, cohesive failure of the easy-adhesion layer can be easily suppressed.

[0112] The resin constituting the easy-adhesion layer preferably has a glass transition temperature of 30° C. or higher, more preferably 50° C. or higher, and even more preferably 70° C. or higher. The resin preferably has a glass transition temperature of 120° C. or lower, more preferably 110° C. or lower, and even more preferably 90° C. or lower. By setting the glass transition temperature of the resin constituting the easy-adhesion layer to 30° C. or higher, it is possible to easily prevent the easy-adhesion layer from flowing due to heat during processing, which causes internal stress, and therefore it is possible to easily set the average value of δq / δa and the variation coefficient of δq / δa within the above range. Examples of heat during processing include heat during a drying process of the coating liquid for the functional layer and heat caused by heating when bonding the optical laminate to a polarizer. By setting the glass transition temperature of the resin constituting the easy-adhesion layer to 120° C. or lower, it is possible to easily suppress the generation of stress due to the difference in thermal behavior between the easy-adhesion layer and the polyester film caused by heat during processing, and thus it is possible to suppress the generation of cracks in the easy-adhesion layer due to the stress. Therefore, by setting the glass transition temperature of the resin constituting the easy-adhesion layer to 120° C. or lower, it is possible to easily set the average value of δq / δa and the coefficient of variation of δq / δa in the above range.

[0113] The easy-adhesion layer may contain additives such as a refractive index adjuster, a dye, a pigment, a leveling agent, an ultraviolet absorber, an antioxidant, and a light stabilizer; and a crosslinking agent for adjusting hardness or viscosity, within a range that does not impair the effects of the present disclosure. Examples of the crosslinking agent include non-yellowing type XDI-based, IPDI-based, and HDI-based isocyanates, and ionizing radiation-curable polyfunctional monomers.

[0114] The adhesive layer may be formed by an in-line coating method in which coating is carried out during the formation of the polyester film, or by an off-line coating method in which coating is carried out after the formation of the polyester film. In the in-line coating method and the offline coating method, it is preferable to use a coating liquid for an easy-adhesion layer containing a component constituting the easy-adhesion layer. For example, the easy-adhesion layer can be formed by applying the coating liquid for an easy-adhesion layer on a polyester film by a general-purpose coating method and drying it. In this case, the drying time is preferably 120 seconds or less, more preferably 90 seconds or less. By setting the drying time to 120 seconds or less, phase separation of the components constituting the easy-adhesion layer can be suppressed, and the average value of δq / δa and the coefficient of variation of δq / δa can be easily set to the above range. If the drying time is too short, the coating surface may become rough and the optical properties may deteriorate. For this reason, the drying time is preferably 15 seconds or more, more preferably 20 seconds or more. The drying time can be adjusted by the drying temperature and drying wind speed. The direction of the drying air is preferably opposite to the conveying direction of the polyester film. By making the direction of the drying air and the conveying direction of the polyester film have the above-mentioned relationship, the drying time of the coating liquid for the easy-adhesion layer can be dramatically shortened without excessively increasing the drying temperature. The drying temperature of the coating liquid for the easy-adhesion layer is preferably 50° C. or higher and 200° C. or lower, more preferably 60° C. or higher and 150° C. or lower. By setting the drying temperature at 50° C. or higher, the drying time of the coating liquid for the easy-adhesion layer can be easily shortened, and therefore, phase separation of the components constituting the easy-adhesion layer can be easily suppressed. By setting the drying temperature at 200° C. or lower, thermal decomposition of the components constituting the easy-adhesion layer can be easily suppressed.

[0115] The coating liquid for the easy-adhesion layer preferably contains a solvent to make the components constituting the easy-adhesion layer dissolvable or dispersible and to adjust the viscosity. Examples of the solvent include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ethers such as dioxane and tetrahydrofuran, etc.; aliphatic hydrocarbons such as hexane, etc.; alicyclic hydrocarbons such as cyclohexane, etc.; aromatic hydrocarbons such as toluene and xylene, etc.; halogenated carbons such as dichloromethane and dichloroethane, etc.; esters such as methyl acetate, ethyl acetate, butyl acetate, etc.; alcohols such as isopropanol, butanol, cyclohexanol, etc.; cellosolves such as methyl cellosolve and ethyl cellosolve, glycol ethers such as propylene glycol monomethyl ether acetate, etc.; cellosolve acetates, sulfoxides such as dimethyl sulfoxide, etc.; amides such as dimethylformamide, dimethylacetamide, etc.; and mixtures of these may also be used.

[0116] If the drying time of the solvent in the coating liquid for the easy-adhesion layer is too long, the components constituting the easy-adhesion layer are likely to undergo phase separation. For this reason, it is preferable that the solvent in the coating liquid for the easy-adhesion layer contains a solvent having a high evaporation rate. On the other hand, if the drying time of the solvent in the coating solution for the easy-adhesion layer is too short, the coating surface is likely to become rough. For this reason, it is preferable to use a mixture of a solvent having an extremely fast evaporation rate and a solvent having an appropriately fast evaporation rate in the coating solution for the easy-adhesion layer. In this specification, a solvent having an extremely fast evaporation rate means a solvent having an evaporation rate of 280 or more when the evaporation rate of butyl acetate is taken as 100. In addition, in this specification, a solvent having a moderately fast evaporation rate means a solvent having an evaporation rate of 150 or more and less than 280 when the evaporation rate of butyl acetate is taken as 100.

[0117] The solvent having an extremely fast evaporation rate preferably has an evaporation rate of 320 or more and 430 or less, and more preferably has an evaporation rate of 340 or more and 400 or less. Examples of the solvent having an extremely fast evaporation rate include methyl ethyl ketone with an evaporation rate of 370 and normal heptane with an evaporation rate of 362. The solvent having a moderately fast evaporation rate has an evaporation rate of preferably 170 to 250, more preferably 180 to 220. Examples of the solvent having a moderately fast evaporation rate include toluene with an evaporation rate of 200 and propyl acetate with an evaporation rate of 214.

[0118] In the solvents of the coating liquid for the easy-adhesion layer, the mass ratio of the solvent having an extremely fast evaporation rate to the solvent having an appropriately fast evaporation rate is preferably 50:50 to 90:10, and more preferably 70:30 to 85:15.

[0119] In order to easily suppress phase separation, the coating liquid for the easy-adhesion layer has a lower limit of solid content of preferably 2% by mass or more, more preferably 4% by mass or more. In addition, the content of the solvent in the coating liquid for the easy-adhesion layer has an upper limit of solid content of preferably 30% by mass or less, more preferably 10% by mass or less.

[0120] The dry coating amount of the easy-adhesion layer is 0.05 g / m 2 More than 0.75g / m 2The thickness of the easy-adhesion layer is not particularly limited, but is preferably 10 nm or more and 600 nm or less, more preferably 20 nm or more and 300 nm or less, and even more preferably 50 nm or more and 200 nm or less. In order to suppress interference fringes, the thickness of the easy-adhesion layer is preferably thin.

[0121] In this specification, the thickness of the easy-adhesion layer and the functional layer can be calculated by selecting 20 arbitrary points on a cross-sectional photograph taken by a scanning transmission electron microscope (STEM) and averaging the 20 points. However, the 20 points should be selected so that they are not biased. The accelerating voltage and magnification of the STEM may be set according to the layer to be measured.

[0122] <Size, shape, etc.> The polyester film with an easy-adhesion layer may be in the form of a sheet cut to a predetermined size, or in the form of a roll obtained by winding a long sheet into a roll. The size of the sheet is not particularly limited, but the maximum diameter is about 2 inches to 500 inches. The "maximum diameter" refers to the maximum length when any two points on the polyester film are connected. For example, when the polyester film is rectangular, the diagonal line of the rectangle is the maximum diameter. When the polyester film is circular, the diameter of the circle is the maximum diameter. The width and length of the roll are not particularly limited, but generally, the width is about 500 mm to 8000 mm, and the length is about 100 m to 10000 m. The polyester film in the roll form can be cut into sheets according to the size of an image display device or the like. When cutting, it is preferable to remove the end of the roll, which has unstable physical properties. The shape of the sheet is not particularly limited, and may be, for example, a polygon such as a triangle, a rectangle, or a pentagon, a circle, or a random, indefinite shape. More specifically, when the polyester film is rectangular, the aspect ratio is not particularly limited as long as it does not cause any problems as a display screen. For example, the aspect ratio may be 1:1, 4:3, 16:10, 16:9, 2:1, 5:4, 11:8, etc.

[0123] [Optical laminate] The optical laminate of the present disclosure has one or more functional layers on the easy-adhesion layer of the polyester film of the present disclosure described above. Fig. 1 is a cross-sectional view showing an embodiment of an optical laminate 1000 of the present disclosure. The optical laminate 1000 of Fig. 1 has a polyester film 100, an easy-adhesion layer 200, and a functional layer 300 in this order.

[0124] <Functional layer> The functional layer may be a single layer or a multilayer. Examples of layers constituting the functional layer include a hard coat layer, an antiglare layer, an antireflection layer, a selective wavelength absorption layer, an antifouling layer, and an antistatic layer. The functional layer may have a plurality of functions in one layer. Among the functional layers, the antireflection layer may have a single-layer structure or a multi-layer structure. The single-layer antireflection layer may be a single layer of a low refractive index layer. The multi-layer antireflection layer may be a two-layer structure of a high refractive index layer and a low refractive index layer, and may also be a structure of three or more layers. Examples of the functional layer formed on the easy-adhesion layer include the following B1 to B7. B1: Single layer hard coat layer B2: Single layer anti-glare layer B3: A multi-layer structure having a hard coat layer and an anti-reflection layer in this order. B4: Multilayer structure having an antiglare layer and an antireflection layer in this order B5: Multilayer structure having a hard coat layer and an antifouling layer in this order B6: Multilayer structure having an antiglare layer and an antifouling layer in this order B7: A multi-layer structure having a hard coat layer, an anti-reflection layer, and an anti-fouling layer in this order.

[0125] Of the one or more functional layers, the functional layer in contact with the easy-adhesion layer preferably contains a cured product of an ionizing radiation curable resin composition. The functional layer in contact with the easy-adhesion layer is preferably a hard coat layer or an antiglare layer. When the functional layer in contact with the easy-adhesion layer contains a cured product of an ionizing radiation curable resin composition, the adhesion of the optical laminate is likely to decrease. However, since the average value of δq / δa on the surface of the easy-adhesion layer of the optical laminate of the present disclosure is a predetermined value, the adhesion of the optical laminate can be easily improved even if the functional layer in contact with the easy-adhesion layer contains a cured product of an ionizing radiation curable resin composition. Furthermore, when the functional layer in contact with the easy-adhesion layer contains a cured product of an ionizing radiation curable resin composition, the pencil hardness of the optical laminate can be easily increased.

[0126] Of the one or more functional layers, the functional layer in contact with the easy-adhesion layer preferably contains a cured product of an ionizing radiation curable resin composition and has a thickness of 0.5 μm or more. This configuration makes it easier to improve the pencil hardness of the optical laminate. The thickness of the functional layer in contact with the easy-adhesion layer is more preferably 1.0 μm or more, and even more preferably 2.0 μm or more, and the upper limit is preferably 20.0 μm or less, more preferably 10.0 μm or less, more preferably 7.0 μm or less, and more preferably 5.0 μm or less. The functional layer in contact with the easy-adhesion layer is preferably a hard coat layer or an antiglare layer. Preferred embodiments of the thickness range of the functional layer in contact with the easy-adhesion layer include 0.5 μm or more and 20.0 μm or less, 0.5 μm or more and 10.0 μm or less, 0.5 μm or more and 7.0 μm or less, 0.5 μm or more and 5.0 μm or less, 1.0 μm or more and 20.0 μm or less, 1.0 μm or more and 10.0 μm or less, 1.0 μm or more and 7.0 μm or less, 1.0 μm or more and 5.0 μm or less, 2.0 μm or more and 20.0 μm or less, 2.0 μm or more and 10.0 μm or less, 2.0 μm or more and 7.0 μm or less, and 2.0 μm or more and 5.0 μm or less.

[0127] The surface of the optical laminate having the functional layer preferably has a contact angle with pure water of 80 degrees or more, more preferably 85 degrees or more, more preferably 90 degrees or more, more preferably 95 degrees or more, and more preferably 100 degrees or more. By making the contact angle 80 degrees or more, the slipperiness when another member contacts the surface of the optical laminate is improved, so that stress is less likely to occur. Therefore, it is easy to improve the adhesion of the optical laminate. That is, by laminating a functional layer with an adjusted contact angle on the easy-adhesion layer of the polyester film with an easy-adhesion layer of the present disclosure, in which the average value of δq / δa is within a predetermined range, it is easy to improve the adhesion of the optical laminate. If the contact angle of pure water is too large, the functional layer located on the surface side of the optical laminate will contain a large amount of antifouling agent. This may result in a decrease in physical properties such as the surface hardness of the optical laminate. For this reason, the contact angle is preferably 130 degrees or less, and more preferably 120 degrees or less. In this specification, the contact angle refers to the static contact angle measured by the θ / 2 method. The pure water may be any general-purpose pure water, and generally has a resistivity of 0.1 MΩ·cm or more and 15 MΩ·cm or less. Preferred embodiments of the contact angle include 80 degrees or more and 130 degrees or less, 80 degrees or more and 120 degrees or less, 85 degrees or more and 130 degrees or less, 85 degrees or more and 120 degrees or less, 90 degrees or more and 130 degrees or less, 90 degrees or more and 120 degrees or less, 95 degrees or more and 130 degrees or less, 95 degrees or more and 120 degrees or less, 100 degrees or more and 130 degrees or less, and 100 degrees or more and 120 degrees or less.

[0128] The functional layer contains, for example, a binder resin and, if necessary, an additive. The thickness of the functional layer may be appropriately selected depending on the function to be imparted.

[0129] The functional layer preferably contains a cured product of a curable resin composition as a binder resin. Examples of the cured product of the curable resin composition include a cured product of a thermosetting resin composition and a cured product of an ionizing radiation curable resin composition, and the cured product of an ionizing radiation curable resin composition is preferred in order to increase the pencil hardness.

[0130] The ratio of the cured product of the curable resin composition to the total binder resin in the functional layer is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 100% by mass.

[0131] The thermosetting resin composition is a composition that contains at least a thermosetting resin, and is a resin composition that is cured by heating. Examples of the thermosetting resin include acrylic resin, urethane resin, phenol resin, urea melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to the curable resin as required.

[0132] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group. In this specification, the "compound having an ionizing radiation curable functional group" may be referred to as an "ionizing radiation curable compound". Ionizing radiation refers to electromagnetic waves or charged particle beams that have an energy quantum capable of polymerizing or crosslinking molecules. Usually, ultraviolet rays or electron beams are used, but other types of radiation, such as electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion beams, can also be used.

[0133] Examples of the ionizing radiation curable functional group include ethylenically unsaturated bond groups such as (meth)acryloyl group, vinyl group, allyl group, etc., as well as epoxy group, oxetanyl group, etc. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, a compound having two or more ethylenically unsaturated bond groups is more preferred, and among these, a polyfunctional (meth)acrylate compound having two or more ethylenically unsaturated bond groups is even more preferred.

[0134] As the polyfunctional (meth)acrylate compound, both monomers and oligomers can be used, but it is preferable that the compound contains an oligomer. That is, it is preferable that the functional layer contains a cured product of a polyfunctional (meth)acrylate oligomer as a binder resin. In particular, it is preferable that the functional layer in contact with the easy-adhesion layer contains a cured product of a polyfunctional (meth)acrylate oligomer as a binder resin. The cured product of the polyfunctional (meth)acrylate oligomer can suppress excessive curing shrinkage of the functional layer while improving the surface hardness of the optical laminate. Therefore, it is possible to easily improve the adhesion of the optical laminate while increasing the pencil hardness of the optical laminate. In order to make it easier to balance the pencil hardness and adhesion of the optical laminate, it is more preferable that the polyfunctional (meth)acrylate compound contains an oligomer and a monomer. That is, it is preferable that the functional layer contains a cured product of a polyfunctional (meth)acrylate oligomer and a cured product of a polyfunctional (meth)acrylate monomer as a binder resin. In particular, it is preferable that the functional layer in contact with the easy-adhesion layer contains a cured product of a polyfunctional (meth)acrylate oligomer and a cured product of a polyfunctional (meth)acrylate monomer as a binder resin.

[0135] When an oligomer and a monomer are used as the polyfunctional (meth)acrylate compound, the mass ratio of the oligomer to the monomer is preferably 5:95 to 95:5, more preferably 50:50 to 85:15, and further preferably 60:40 to 80:20.

[0136] Examples of the polyfunctional (meth)acrylate oligomer include (meth)acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate. The urethane (meth)acrylate can be obtained, for example, by reacting a polyhydric alcohol and an organic diisocyanate with a hydroxy (meth)acrylate.

[0137] The weight average molecular weight of the polyfunctional (meth)acrylate oligomer is preferably such that the lower limit is 500 or more, more preferably 1000 or more, and is preferably such that the upper limit is 5000 or less, more preferably 3000 or less. By setting the weight-average molecular weight of the oligomer to 500 or more, it is possible to easily suppress excessive cure shrinkage of the functional layer. Also, by setting the weight-average molecular weight of the oligomer to 5,000 or less, it is possible to easily suppress a decrease in pencil hardness. Examples of the range of the weight average molecular weight of the polyfunctional (meth)acrylate oligomer include 500 or more and 5,000 or less, 500 or more and 3,000 or less, 1,000 or more and 5,000 or less, and 1,000 or more and 3,000 or less. In this specification, the weight average molecular weight and number average molecular weight refer to values ​​calculated as polystyrene standards measured by gel permeation chromatography.

[0138] Among the polyfunctional (meth)acrylate compounds, examples of bifunctional (meth)acrylate monomers include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxydiacrylate, bisphenol A tetrapropoxydiacrylate, and 1,6-hexanediol diacrylate. Examples of trifunctional or higher (meth)acrylate monomers include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate. The (meth)acrylate monomer may have a part of its molecular skeleton modified, for example, a (meth)acrylate monomer modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, or the like may be used.

[0139] For the purpose of adjusting the viscosity of the coating liquid for the functional layer, a monofunctional (meth)acrylate may be added as an ionizing radiation curable compound. Examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate. The above ionizing radiation curable compounds may be used alone or in combination of two or more. In addition to the ionizing radiation curable compound, a polymer may be added to the functional layer coating solution in order to adjust the viscosity. Examples of the polymer include those having a weight average molecular weight of more than 5,000 and not more than 200,000.

[0140] When the ionizing radiation curable compound is an ultraviolet ray curable compound, the ionizing radiation curable resin composition preferably contains additives such as a photopolymerization initiator and a photopolymerization accelerator. The photopolymerization initiator may be one or more selected from acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzil dimethyl ketal, benzoyl benzoate, α-acyloxime ester, anthraquinone, halogenoketone, thioxanthones, etc. Among these, α-hydroxyalkylphenone, which is less prone to yellowing, is preferred. The photopolymerization accelerator can reduce polymerization inhibition caused by air during curing and increase the curing speed, and examples of the accelerator include one or more types selected from p-dimethylaminobenzoic acid isoamyl ester, p-dimethylaminobenzoic acid ethyl ester, etc.

[0141] The functional layer may contain additives as necessary. The additive may be appropriately selected from general-purpose materials depending on the function to be imparted to the functional layer. For example, when the functional layer is to be imparted with antiglare properties, it is preferable to include organic particles and / or inorganic particles as additives. When the functional layer is to be imparted with antireflection properties, it is preferable to include a refractive index adjusting material such as a high refractive index material and a low refractive index material as additives. When the functional layer is to be imparted with antifouling properties, it is preferable to include an antifouling agent as additives. Further examples of additives include antistatic agents, leveling agents, ultraviolet absorbers, dyes, pigments, conductive particles, flocculants, defoamers, antioxidants, and light stabilizers.

[0142] <Physical Properties> The optical laminate preferably has a total light transmittance according to JIS K7361-1:1997 of 50% or more, more preferably 80% or more, and even more preferably 90% or more. The total light transmittance and the haze described later are measured with the light incident surface facing the polyester film. The total light transmittance and the haze described later can be measured, for example, with a haze meter (product number: HM-150) manufactured by Murakami Color Research Laboratory.

[0143] The haze of the optical laminate according to JIS K7136:2000 is preferably at least 0.3%, more preferably at least 0.4%, and even more preferably at least 0.5%, and is preferably at most 10%, more preferably at most 7%, and even more preferably at most 5%.

[0144] <Size, shape, etc.> The optical laminate may be in the form of a sheet cut to a predetermined size, or in the form of a roll obtained by winding a long sheet into a roll. The size of the sheet is not particularly limited, but the maximum diameter is about 2 inches to 500 inches. The "maximum diameter" refers to the maximum length when any two points on the optical laminate are connected. For example, when the optical laminate is rectangular, the diagonal line of the rectangle is the maximum diameter. When the optical laminate is circular, the diameter of the circle is the maximum diameter. The width and length of the roll are not particularly limited, but generally, the width is about 500 mm to 8000 mm, and the length is about 100 m to 10000 m. The optical laminate in the form of a roll can be cut into sheets according to the size of an image display device or the like. When cutting, it is preferable to exclude the ends of the roll, which have unstable physical properties. The shape of the sheet is not particularly limited, and may be, for example, a polygon such as a triangle, a rectangle, or a pentagon, a circle, or a random, indefinite shape. More specifically, when the optical laminate is a rectangle, the aspect ratio is not particularly limited as long as it does not cause any problems as a display screen. For example, horizontal: vertical = 1:1, 4:3, 16:10, 16:9, 2:1, 5:4, 11:8, etc.

[0145] [Polarizing plate] The polarizing plate of the present disclosure has a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical laminate of the present disclosure described above, and the optical laminate is arranged so that the surface on the functional layer side faces the opposite side to the polarizer.

[0146] <Polarizer> Examples of polarizers include sheet-type polarizers such as polyvinyl alcohol films, polyvinyl formal films, polyvinyl acetal films, and saponified ethylene-vinyl acetate copolymer films dyed with iodine or the like and stretched, wire grid-type polarizers made of a large number of metal wires arranged in parallel, coating-type polarizers coated with lyotropic liquid crystal or a dichroic guest-host material, and multilayer thin film-type polarizers. These polarizers may be reflective polarizers that have the function of reflecting polarized components that are not transmitted.

[0147] <Transparent protection plate> A first transparent protective plate is disposed on one side of the polarizer, and a second transparent protective plate is disposed on the other side of the polarizer. At least one of the first transparent protective plate and the second transparent protective plate is the optical laminate of the present disclosure described above.

[0148] Examples of the first transparent protective plate and the second transparent protective plate other than the optical laminate include plastic films and glass. Examples of the plastic film include polyester films, polycarbonate films, cycloolefin polymer films, and acrylic films, and stretched films thereof are preferred in order to improve mechanical strength. Examples of the glass include alkali glass, nitride glass, soda-lime glass, borosilicate glass, and lead glass. In addition, it is preferable that the glass as the transparent protective plate for protecting the polarizer is also used as another member of the image display device. For example, it is preferable that the glass substrate of the liquid crystal display element is also used as the transparent protective plate for protecting the polarizer. The polarizer and the transparent protective plate are preferably attached to each other via an adhesive, which may be a general-purpose adhesive, and is preferably a PVA-based adhesive.

[0149] The polarizing plate of the present disclosure may be the optical laminate of the present disclosure in which both the first transparent protective plate and the second transparent protective plate are described above, but it is preferable that one of the first transparent protective plate and the second transparent protective plate is the optical laminate of the present disclosure. In addition, when the polarizing plate of the present disclosure is used as a polarizing plate arranged on the light exit surface side of a display element, it is preferable that the transparent protective plate on the light exit surface side of the polarizer is the optical laminate of the present disclosure. On the other hand, when the polarizing plate of the present disclosure is used as a polarizing plate arranged on the opposite side to the light exit surface of a display element, it is preferable that the transparent protective plate on the opposite side to the light exit surface of the polarizer is the optical laminate of the present disclosure.

[0150] [Surface plate] The surface plate of the present disclosure is a surface plate formed by laminating an optical laminate onto a resin plate or a glass plate, the optical laminate being the optical laminate of the present disclosure described above, and the optical laminate being arranged so that the surface on the functional layer side faces the opposite side to the resin plate or the glass plate.

[0151] The face plate of the present disclosure can be used, for example, as a face plate for an image display device. The face plate of the present disclosure can also be used as a face plate for protecting an object such as a clock, a painting, etc. Furthermore, the face plate of the present disclosure can also be used as a member for a show window or a showcase.

[0152] The surface plate for the image display device is preferably arranged so that the surface on which the optical laminate is bonded faces the front side. In other words, the surface plate for the image display device is preferably arranged so that the surface on which the optical laminate is bonded faces the opposite side to the display element. The surface plate for protecting the article is preferably disposed so that the surface on the side to which the optical laminate is attached faces away from the article.

[0153] As the resin plate or glass plate, a resin plate or glass plate that is generally used as a surface plate can be used.

[0154] The thickness of the resin plate or glass plate is preferably 10 μm or more in order to improve strength. The upper limit of the thickness of the resin plate or glass plate is usually 5000 μm or less, but in recent years, thinner image display devices are preferred, so the thickness is preferably 1000 μm or less, more preferably 500 μm or less, and even more preferably 100 μm or less. Examples of the range of the thickness of the resin plate or glass plate include 10 μm or more and 5000 μm or less, 10 μm or more and 1000 μm or less, 10 μm or more and 500 μm or less, and 10 μm or more and 100 μm or less.

[0155] [Image display panel] The image display panel of the present disclosure is obtained by disposing the above-mentioned optical laminate of the present disclosure on a display element.

[0156] In the image display panel, the optical laminate is preferably disposed so that the surface on the functional layer side faces the opposite side to the display element. Also, the optical laminate is preferably disposed on the outermost surface of the image display panel.

[0157] Examples of the display element include a liquid crystal display element, an EL display element such as an organic EL display element and an inorganic EL display element, a plasma display element, and an LED display element such as a mini LED display element and a micro LED display element. Examples of the display element include a laser hologram display element. These display elements may have a touch panel function inside the display element. Examples of the liquid crystal display system of the liquid crystal display element include the IPS system, VA system, multi-domain system, OCB system, STN system, TSTN system, and ferroelectric liquid crystal system. When the display element is a liquid crystal display element, a backlight is required. The backlight is disposed on the opposite side of the liquid crystal display element from the side having the optical laminate. Examples of the backlight include a backlight using quantum dots and a backlight using white light emitting diodes. The image display panel may be a foldable image display panel or a rollable image display panel, or may be an image display panel with a touch panel.

[0158] The size of the image display panel is not particularly limited, but the maximum diameter is about 2 inches to 500 inches. The maximum diameter means the maximum length when connecting any two points on the surface of the image display panel.

[0159] [Image display device] The image display device of the present disclosure includes the image display panel of the present disclosure described above. In the image display device, the optical laminate is preferably disposed so that the surface on the functional layer side faces the opposite side to the display element. Also, the optical laminate is preferably disposed on the outermost surface of the image display device.

[0160] It is preferable that the image display device according to the present disclosure further includes a drive control unit electrically connected to the image display panel, and a housing that houses the image display panel, the drive control unit, and the like. When the display element is a liquid crystal display element, the image display device of the present disclosure requires a backlight, which is disposed on the side opposite to the light exit surface of the liquid crystal display element. The size of the image display device is not particularly limited, but the maximum diameter of the effective display area is about 2 inches to 500 inches.

[0161] The effective display area of ​​an image display device is an area in which an image can be displayed. For example, when the image display device has a housing that surrounds a display element, the effective display area is the area inside the housing. The maximum diameter of the effective display area is the maximum length between any two points within the effective display area. For example, if the effective display area is rectangular, the maximum diameter is the diagonal of the rectangle. If the effective display area is circular, the maximum diameter is the diameter of the circle. EXAMPLES

[0162] The present disclosure will be specifically described below with reference to examples and comparative examples. The present disclosure is not limited to the embodiments described in the examples.

[0163] 1. Evaluation and measurement The following measurements and evaluations were carried out on the polyester films with an easy-adhesion layer and the optical laminates obtained in the examples and comparative examples. The results are shown in Tables 1 and 2. Unless otherwise specified, the atmosphere during each measurement and evaluation was a temperature of 23±5°C and a relative humidity of 40% to 65%. Samples for measurement and evaluation were clean, flat, and free of defects. Furthermore, unless otherwise specified, the target samples were exposed to the above atmosphere for 30 minutes to 60 minutes before the start of each measurement and evaluation.

[0164] 1-1.Pencil hardness The pencil hardness of the polyester film with the easy-adhesion layer of the examples and comparative examples was measured. The method for measuring the pencil hardness was in accordance with the procedures (1) to (6) in the main text of the specification. The pencil hardness was measured before the easy-adhesion layer was formed. For commercially available polyester films with easy-adhesion formed on one side in advance, the pencil hardness of the side on which the easy-adhesion layer was not formed was measured. The pencil hardness was measured on both the slow axis and the fast axis.

[0165] 1-2. Calculation of the average value of δq / δa Samples of 5 mm × 5 mm were cut out from the polyester films with an easy-adhesion layer of the examples and comparative examples. Then, for the said samples, a 10 μm × 10 μm region on the surface of the adhesion layer was measured in the phase mode of an atomic force microscope. The measuring apparatus and measuring conditions are as follows. Seven 2 μm × 2 μm measurement and evaluation regions were selected from within the 10 μm × 10 μm measurement region. The said seven locations were selected from regions where the maximum height of the amplitude measured by the atomic force microscope is 90 nm or less and the arithmetic mean height of the amplitude is 10 nm or less. The δa, δq, and δq / δa of the seven measurement and evaluation regions were calculated respectively. Based on the δa and δq of the five measurement and evaluation regions obtained by excluding the maximum value and the minimum value from the δq / δa of the seven locations, the average value of δq / δa and the coefficient of variation of δq / δa were calculated. In the following measuring apparatus, when a 2 μm × 2 μm measurement and evaluation region is selected on the screen, the δa and δq of the selected measurement and evaluation region are automatically displayed (however, for the settings of the following measuring apparatus, on the display screen of the following measuring apparatus, the item corresponding to δa is displayed as "Ra" and the item corresponding to δq is displayed as "Rq").

[0166] <Measuring apparatus> Product name "SPM-9600" manufactured by Shimadzu Corporation <Analysis software> SPM Manager <AFM analysis conditions> Tilt correction: Line fit <Cantilever used> Product number "NCHR" of Nanoworld (Resonance frequency: 320 kHz, spring constant 42 N / m) <Measurement mode> Phase (In the "phase mode" of the above measuring apparatus, not only the phase but also the amplitude is measured.)

[0167] <Measurement conditions> - Amplitude · Phase - · Sensitivity: ×2 · Phase offset: 95.00 deg - XY control - · Scanning range: 10.0000 μm Scanning speed: 1.00Hz Resolution: 512 x 512 Offset X: 0.0000μm Offset Y: 0.0000μm Scan angle: 0.0000deg -Z Control- Operating point: 0.228V P-Gain: 0.001 I-Gain: 15000.000 Offset Z: 0.0630μm

[0168] 1-3. Adhesion A cutter blade was inserted from the surface of the hard coat layer side of the optical laminate of the examples and comparative examples to form 100 grid-like cuts (number of cuts: 11 vertical and horizontal cuts, cut interval: 1 mm). The cutter blade used was NT Corporation's product number "BA-52P". Next, an adhesive tape (Nichiban Corporation, product name "Cellotape (registered trademark)") was attached to the surface of the optical laminate with the grid formed thereon, and the adhesive tape was peeled off to perform a peel test in accordance with the cross-cut method specified in JIS K5600-5-6:1999. The adhesion of the optical laminate of the examples and comparative examples was evaluated according to the following evaluation criteria. <Evaluation criteria> A: The number of peeled squares is 0 and no squares are missing. B: The number of peeled off squares is 0, but there are some areas where parts of the squares are missing, such as along the cuts. C: The number of peeled squares is 1 or more.

[0169] 1-4. Total light transmittance (Tt) and haze (Hz) Using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory), the total light transmittance according to JIS K7361-1:1997 and the haze according to JIS K7136:2000 were measured for the optical laminates of the examples and comparative examples. The light incident surface was the polyester film side.

[0170] 1-5. Measurement of erosion rate The erosion rate of the polyester film was measured using an erosion rate measuring device (MSE test device from Palmeso Co., Ltd., product number "MSE-A203", nozzle cross-sectional shape is a square of 1 mm x 1 mm, cross-sectional profile measuring means: stylus type) for the polyester film with the easy-adhesion layer of the examples and comparative examples. 0-20 and σ 0-20 / E 0-20 The measurement was carried out three times for each polyester film, and the average value of the three measurements was calculated as E 0-20 and σ 0-20 / E 0-20 The measurement area for the erosion rate was 1 mm × 1 mm. The erosion rate was measured before the formation of the easy-adhesion layer. For commercially available polyester films with easy-adhesion formed on one side, the pencil hardness of the side on which the easy-adhesion layer was not formed was measured. The erosion rate of each sample was measured after the following calibration using a standard acrylic plate. The test liquid was prepared before the calibration, and a preliminary dispersion run was performed before the calibration. The standard acrylic plate had an AcE (average erosion rate of the acrylic plate measured under measurement condition A) in the specification within the range of 1.786 μm / g to 1.974 μm / g.

[0171] (0-1) Preparation of test solution In a beaker, pure water, a dispersant (trade name "Demol N" of Wako Pure Chemical Industries, Ltd.), and spherical silica with an average particle size (median diameter) of 3.94 μm (model number "MSE-BS-5-3" designated by Palmeso Co., Ltd., full width at half maximum of particle size distribution: 4.2 μm) were mixed in a mass ratio of 968:2:30 to prepare a test liquid, which was then mixed with a glass rod. After placing the prepared test liquid and a stirrer in a container (pot), the pot was covered and a clamp was attached. Next, the pot was placed in a measuring device. In this example, the model number "MSE-BS-5-3" designated by Palmeso Co., Ltd. was the product number "BS5-3" of Potters-Ballotini Co., Ltd. (0-2) Distributed operation After placing the pot containing the test liquid in the measuring device, a dummy sample was set on the sample mounting base. Next, the buttons "Erosion Force Setting" and "Execute" were pressed in sequence on the operation panel of the main body of the measuring device. Next, the specified values ​​were entered for the flow rates of the test liquid and compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle, and the test liquid was projected onto the dummy sample. After stopping the projection, the buttons "Back," "Complete," and "Confirm" were pressed in sequence on the same operation panel.

[0172] (1) Calibration A 4 mm thick acrylic plate, which is a calibration sample, was fixed to the sample mounting stage of the measurement device via double-sided tape (Nitto Denko America's "Kapton double-stick tape", product number: P-223 1-6299-01). The acrylic plate was a PMMA plate. Next, the sample mounting stage to which the acrylic plate was fixed was set in the measuring device. Next, the microgauge was unlocked and the height of the sample mounting table was adjusted with the height gauge. The distance between the injection hole of the measuring device and the acrylic plate was adjusted to 4 mm. Next, after pressing the button "To processing condition input screen" on the operation panel of the main body of the measuring device, the settings were made as "Step number: 1, specified injection amount g x 1 time." The injection amount was set to 4 g. Next, the buttons on the operation panel "Settings complete," "Start operation," and "Yes" were pressed in sequence. The flow rates of the test liquid and compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle were maintained at the values ​​input in "(0-2) Distributed operation." Next, "Online" was clicked on the operation screen of the data processing PC to release the online state and change it to offline state. Next, "Down" was clicked on the operation screen to lower the stylus of the stylus step gauge in the cross-sectional profile acquisition section. Next, it was confirmed that the microgauge was unlocked, and the microgauge was rotated upward. At this time, the red arrow on the monitor was adjusted so that it was in the center. This adjustment brings the stylus of the stylus step gauge into contact with the surface of the calibration sample, and allows the 0 point of the z-axis, which is the height direction, to be adjusted. The microgauge was then switched from unlocked (off) to on. Next, "Raise" was clicked to raise the stylus of the stylus step gauge in the cross-sectional profile acquisition section. Next, "offline" was clicked on the operation screen of the data processing PC to cancel the offline state and change it to online. Next, the cover of the measuring device body was closed, the "Confirm" button on the operation panel of the measuring device body was pressed, and 4 g of the test liquid was sprayed. After stopping the injection of the test liquid, click "Execute" to calculate the erosion rate. If the erosion rate was within ±5% of the reference value of 1.88 (μm / g), the calibration was terminated. If the erosion rate was outside the range, the flow rate of the test liquid, the flow rate of the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle were adjusted, and the calibration was repeated until the erosion rate was within the range.

[0173] (2) Measurement of the erosion rate of each sample (2-1) Mounting the sample A laminate was prepared by attaching the sample (plastic film of the Examples and Comparative Examples) to a stainless steel plate, and the laminate was fixed to a sample mounting table using double-sided tape (Nitto Denko America, Inc., "Kapton double-stick tape", product number: P-223 1-6299-01). The sample was 1 cm x 1 cm in size. Next, the sample mounting stage was set on the measuring device. Then, the lock of the microgauge was released and the height of the sample mounting stage was adjusted with the height gauge. The distance between the injection hole of the measuring device and the plastic film was adjusted to 4 mm. Next, after pressing the button "To processing condition input screen" on the operation panel of the measuring device main body, the number of steps was entered, and the amount of test liquid sprayed (g / time) for each step was entered. The amount sprayed for each step was in the range of 0.5g to 3.0g. The flow rates of the test liquid and compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle were maintained at the conditions that had been passed in "(1) Calibration." Next, he pressed the buttons "Settings complete," "Start operation," and "Yes" on the operation panel in that order. Next, "Online" was clicked on the operation screen of the data processing PC to release the online state and change it to offline state. Next, "Down" was clicked on the operation screen to lower the stylus of the stylus step gauge in the cross-sectional profile acquisition section. Next, it was confirmed that the microgauge was unlocked, and the microgauge was rotated upward. At this time, the red arrow on the monitor was adjusted so that it was in the center. This adjustment brings the stylus of the stylus step gauge into contact with the surface of the calibration sample, and allows the 0 point of the z-axis, which is the height direction, to be adjusted. The microgauge was then switched from unlocked (off) to on. Next, "Raise" was clicked to raise the stylus of the stylus step gauge in the cross-sectional profile acquisition section. Next, "offline" was clicked on the operation screen of the data processing PC to cancel the offline state and change it to online.

[0174] (2-2) Start measurement The cover of the measuring device was closed, and the "Confirm" button on the operation panel of the measuring device was pressed, and a cycle of spraying the test liquid and measuring the cross-sectional profile was repeated until the depth of the cross-sectional profile exceeded 20 μm. Specifically, the cycle was continued until the depth of the cross-sectional profile reached a depth of 25 μm to 30 μm. After the measurement, the attached software "MseCalc" was started and "Analysis Method" was clicked. Next, "Average Value Analysis" was clicked. Next, "Add" on the average value analysis screen was clicked twice, causing "A-1" and "A-2" to appear in the analysis name column. The "Standard" column for "A-1" was double-clicked, causing a "○" to appear in the standard column. Next, click "A-1" on the average value analysis screen to activate it, and manipulate the position of the X-axis position bar. The position of the position bar is determined to be a point in the cross-sectional profile screen where the plastic film is not worn. Next, click A-2 on the average value analysis screen to activate it, and manipulate the position of the X-axis position bar. The position of the position bar determines the deepest part where the plastic film is worn in the cross-sectional profile screen. Next, I clicked on "File List" in the included software. Then, in the "Correction" field on the file list screen, I selected "BS5-3." Next, the cross-sectional profile and erosion rate data for each step are output in CSV format, and the erosion rate E 0-20 Specifically, the erosion rate (corrected) of the data output in CSV format with a depth of 0 μm to 20 μm was averaged to obtain the erosion rate E 0-20 was calculated.

[0175] 1-6.Rainbow unevenness The polyester films with the adhesive layer of the Examples and Comparative Examples were evaluated for rainbow unevenness by the following procedures (1) to (3). (1) The polyester films with easy-adhesion layers of the examples and comparative examples were cut into A4 size samples. (2) The sample prepared in (1) was attached via water to the viewer-side polarizing plate of an image display device having the following configuration. The water present at the interface between the viewer-side polarizing plate and the sample can suppress the optical effect of the surface irregularities of the polarizer protective film of the viewer-side polarizing plate. The sample was arranged so that the direction of the long side of the sample and the direction of the absorption axis of the polarizer of the viewer-side polarizing plate were within a specified angle range. The specified angle range was set to three angles: 0±5 degrees, 45±5 degrees, and 90±5 degrees. The direction of the absorption axis of the polarizer of the viewer-side polarizing plate can be confirmed as follows. <How to check the direction of the absorption axis of the polarizer on the viewing side polarizing plate> A polarizing film with an absorption axis direction marked is placed on an image display device having the following configuration. The polarizing film is slowly rotated and stopped at a position where it becomes completely black. At this position, the direction perpendicular to the markings on the polarizing film is the absorption axis direction of the polarizer of the viewing side polarizing plate. (3) The image display device was turned on in a darkroom environment, and ten evaluators observed the image display device from various angles with the naked eye and evaluated the presence or absence of rainbow unevenness according to the following criteria. The distance between the observer and the image display device was 0.3 to 1.0 m. The image display device had a color temperature of 6500 K, white display, and a brightness of 250 cd / m 2 It turned on under the following conditions. <Configuration of image display device> Backlight source: White LED ·Light source side polarizing plate: It has TAC film as a protective film on both sides of a polarizer made of PVA and iodine. It is arranged so that the absorption axis direction of the polarizer is perpendicular to the horizontal direction of the screen. Image display cell: Liquid crystal cell · Viewer-side polarizing plate: A polarizing plate in which TAC film is used as a polarizer protection film on both sides of a polarizer made of PVA and iodine. The polarizer is arranged so that the absorption axis direction is perpendicular to the parallel direction of the screen. An anti-glare layer is laminated on the polarizer protection film on the viewing side. Size: 20" diagonal <Evaluation criteria> AA: Between 7 and 10 people answered that they could not see the rainbow unevenness in any of the three angle ranges. A: Six people answered that they could not see the rainbow unevenness in any of the three angle ranges. B + :Five people answered that they could not see the rainbow unevenness in any of the three angle ranges. B: Two or more and four or less people answered that they could not see the rainbow unevenness in any of the three angle ranges. C: Less than one person answered that they could not see the rainbow unevenness in any of the three angle ranges.

[0176] 2. Preparation of coating solution for easy adhesion layer 2-1. Coating solution A for easy adhesion layer The following materials were mixed and subjected to an ester exchange reaction at 200° C. for 2 hours to obtain compound 1. Dimethyl terephthalate 106 parts by weight Ethylene glycol 25 parts by weight 25 parts by weight of 1,4-butanediol Zinc acetate 0.1 parts by weight Antimony trioxide 0.1 parts by weight Next, 4.0 parts by mass of fumaric acid was added to compound 1, and an esterification reaction was carried out at 230° C. for 2 hours. Next, a polycondensation reaction was carried out at 250° C. under reduced pressure (3 to 6 mmHg) for 1 hour, to obtain compound 2. 230 parts by mass of methyl ethyl ketone and 120 parts by mass of isopropyl alcohol were added to compound 2. The mixture was stirred while being heated at 70° C. to dissolve compound 2, and resin solution 3 was obtained. To the resin solution 3, 25 parts by mass of m-xylene diisocyanate was added and stirred for 3 hours. Then, the temperature of the reaction vessel was raised to 100° C., and methyl ethyl ketone and isopropyl alcohol were removed, thereby obtaining an easily adhesive resin 4. The adhesive resin 4 was dissolved in a mixed solvent of methyl ethyl ketone and toluene in a mass ratio of 8:2 to obtain an adhesive layer coating solution A having a solid content of 5 mass%. The mass ratio of the polyester component to the polyurethane component of the adhesive layer coating solution A was 8:2.

[0177] 2-2. Coating solution B for easy adhesion layer The following materials were mixed and subjected to an ester exchange reaction at 200° C. for 2 hours to obtain compound 5. Dimethyl terephthalate 106 parts by weight Ethylene glycol 28 parts by weight 1,4-butanediol 30 parts by weight Zinc acetate 0.1 parts by weight Antimony trioxide 0.1 parts by weight Next, 4.0 parts by mass of fumaric acid was added to compound 5, and an esterification reaction was carried out at 230° C. for 2 hours. Next, a polycondensation reaction was carried out at 250° C. under reduced pressure (3 to 6 mmHg) for 1 hour, to obtain compound 6. 230 parts by mass of methyl ethyl ketone and 120 parts by mass of isopropyl alcohol were added to compound 6. The mixture was stirred while being heated at 70° C. to dissolve compound 6, and resin solution 7 was obtained. To the resin solution 7, 45 parts by mass of m-xylene diisocyanate was added and stirred for 3 hours. Then, the temperature of the reaction vessel was raised to 100° C., and methyl ethyl ketone and isopropyl alcohol were removed, thereby obtaining an easily adhesive resin 8. The adhesion-enhancing resin 8 was dissolved in a mixed solvent of methyl ethyl ketone and toluene in a mass ratio of 8:2 to obtain an adhesion-enhancing layer coating solution B having a solid content of 5 mass%. The mass ratio of the polyester component to the polyurethane component of the adhesion-enhancing layer coating solution B was 7:3.

[0178] 2-3. Coating solution C for easy adhesion layer The following materials were mixed to obtain a coating solution C for an easy-adhesion layer. First urethane resin: 12 parts by weight (Dainippon Ink and Chemicals, product name: HYDRAN AP-20, glass transition temperature: 27°C, flow start temperature: 90°C) Second urethane resin: 3 parts by weight (Dainippon Ink and Chemicals, product name: HYDRAN AP-30, glass transition temperature 61°C, flow start temperature 105°C) Hardener 2 parts by weight (Sumitomo Chemical Co., Ltd., product name: Sumimal M30W, main ingredient: methylol melamine) ·Water 85 parts by mass

[0179] 2-4. Coating solution D for easy adhesion layer The following materials were mixed and subjected to a transesterification reaction at 160 to 220° C. by a conventional method to obtain compound 9. Dimethyl terephthalate 34.5 parts by weight 1,4 butanediol 21.1 parts by weight Ethylene glycol 27 parts by weight Tetra-n-butyl titanate 0.05 parts by mass Next, 1.4 parts by mass of fumaric acid and 16 parts by mass of sebacic acid were added to compound 9, and an esterification reaction was carried out at 200 to 220° C., thereby obtaining copolymerized polyester resin 10. 75 parts by mass of copolymerized polyester resin 10 was added to a mixed solvent of 56 parts by mass of methyl ethyl ketone and 19 parts by mass of isopropyl alcohol, and the mixture was stirred at 65° C. to dissolve copolymerized polyester resin 10, thereby obtaining resin solution 11. To the resin solution 11, 15 parts by mass of maleic anhydride was added to obtain a resin solution 12. A resin solution 13 was prepared by dissolving 10 parts by mass of styrene and 1.5 parts by mass of azobisdimethylnitrile in 12 parts by mass of methyl ethyl ketone. The resin solution 13 was dripped into the resin solution 12 at 0.1 ml / min and stirred for 2 hours. 5 parts by mass of methanol was added, and further 300 parts by mass of water and 15 parts by mass of triethylamine were added and stirred for 1 hour. Thereafter, the temperature of the reaction vessel was raised to 100°C, and methyl ethyl ketone, isopropyl alcohol and excess triethylamine were distilled off to obtain an easily adhesive resin 14. The adhesion-enhancing resin 14 was dissolved in a mixed solvent of methyl ethyl ketone and toluene in a mass ratio of 8:2 to obtain an adhesion-enhancing layer coating solution D having a solid content of 5 mass%. The mass ratio of the polyester component to the polyurethane component of the adhesion-enhancing layer coating solution D was 5:5.

[0180] 2-5. Coating solution E for easy adhesion layer Except for changing the amounts of dimethyl terephthalate, ethylene glycol, 1,4-butanediol, and m-xylene diisocyanate to the amounts shown below, the coating solution E for the easy-adhesion layer was obtained in the same manner as the coating solution A for the easy-adhesion layer. The mass ratio of the polyester component and the polyurethane component of the resin in the coating solution E for the easy-adhesion layer was 2:8. Dimethyl terephthalate 106 parts by weight Ethylene glycol 25 parts by weight 25 parts by weight of 1,4-butanediol m-Xylene diisocyanate 0.1 parts by mass

[0181] 2-6. Coating solution F for easy adhesion layer Except for changing the amounts of dimethyl terephthalate, ethylene glycol, 1,4-butanediol, and m-xylene diisocyanate to the amounts shown below, the coating solution F for the easy-adhesion layer was obtained in the same manner as the coating solution A for the easy-adhesion layer. The mass ratio of the polyester component and the polyurethane component of the resin of the coating solution F for the easy-adhesion layer was 88:12. Dimethyl terephthalate 100 parts by weight Ethylene glycol 21.5 parts by weight 1,4-butanediol 21.5 parts by weight m-Xylene diisocyanate 13 parts by weight

[0182] 2-7. Coating solution G for easy adhesion layer Except for changing the amounts of dimethyl terephthalate, ethylene glycol, 1,4-butanediol, and m-xylene diisocyanate to the amounts shown below, the coating solution G for the easy-adhesion layer was obtained in the same manner as the coating solution A for the easy-adhesion layer. The mass ratio of the polyester component and the polyurethane component of the resin of the coating solution G for the easy-adhesion layer was 83:17. Dimethyl terephthalate 100 parts by weight Ethylene glycol 23 parts by weight 1,4-butanediol 23 parts by weight m-Xylene diisocyanate 20 parts by weight

[0183] 3. Preparation and production of PET film, and measurement or calculation of in-plane retardation of PET film As polyester films of the examples and comparative examples, the following PET films 1 to 6 were produced, and the following PET films 7 to 9 were also prepared. In addition, the in-plane retardation (Re) of each PET film was measured using Otsuka Electronics' RETS-100. The measured in-plane retardation of each PET film was divided by the thickness of each PET film to calculate the nx-ny of each PET film. The thickness of each PET film was measured using Nikon's Digimicro (stand + main unit: MS-5C + MH-15M, counter: TC-101A).

[0184] 3-1.PET film 1 1 kg of PET (melting point 258°C, absorption center wavelength: 320 nm) and 0.1 kg of ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) were melt-mixed at 280°C in a kneader to produce pellets containing the ultraviolet absorber. The pellets and PET with a melting point of 258°C were put into a single-screw extruder and melt-mixed at 280°C, extruded from a T-die, and cast onto a cast drum with a controlled surface temperature to obtain a cast film. The amount of ultraviolet absorber in the cast film was 3 parts by mass per 100 parts by mass of PET. (Control of the surface temperature of the cast drum: 45°C at the part where the resin extruded from the T-die adheres; 23°C at the part where the resin peels off. Adjust so that the temperature gradually decreases from the part where the resin adheres to the part where the resin peels off.) The obtained casting film was heated with a group of rolls set at 119°C, and then stretched 5.1 times in the machine direction while being heated from both sides with a radiation heater so that the film temperature at a point 180 mm into the 480 mm stretching section (starting point is stretching roll A, ending point is stretching roll B. Stretching rolls A and B each have two nip rolls) would be 138°C, and then cooled once. The time for the casting film to pass through the stretching section in the machine direction is 0.194 seconds. Next, the uniaxially stretched film was introduced into a tenter, preheated with a group of rolls set at 119 ° C., and then stretched 4.9 times in the film width direction while heat-treating with hot air at 105 ° C. in the first stage and hot air at 140 ° C. in the second stage. Here, when the stretching section in the width direction was divided into two, the film was stretched in two stages so that the stretch amount of the film at the midpoint of the stretching section in the width direction (film width at the measurement point - film width before stretching) was 80% of the stretch amount at the end of the stretching section in the width direction. The film stretched in the width direction was heat-treated in the tenter in stages from 180 ° C. to 245 ° C. in a heat treatment temperature, followed by 1% relaxation treatment in the width direction under the same temperature conditions, further quenched to 100 ° C., and then subjected to 1% relaxation treatment in the width direction, and then wound up to obtain a biaxially stretched PET film 1 having a thickness of 40 μm.

[0185] 3-2.PET film 2 Biaxially stretched PET film 2 was obtained in the same manner as PET film 1. PET film 2 was produced under the same conditions as PET film 1, but due to lot variations, its physical properties are slightly different from those of PET film 1.

[0186] 3-3.PET film 3 Biaxially stretched PET film 3 was obtained in the same manner as PET film 1, except that the time during which the casting film passed through the stretching section in the machine direction was changed to 0.179 seconds and the relaxation treatment after heat treatment and relaxation treatment after quenching were not performed.

[0187] 3-4.PET Film 4 Biaxially stretched PET film 4 was obtained in the same manner as PET film 1, except that the time during which the cast film passed through the stretching section in the machine direction was changed to 0.185 seconds and no relaxation treatment was performed after quenching.

[0188] 3-5.PET Film 5 Biaxially stretched PET film 5 was obtained in the same manner as PET film 1. PET film 5 was produced under the same conditions as PET film 1, but due to lot variation, its physical properties are slightly different from those of PET film 1.

[0189] 3-6.PET Film 6 Biaxially stretched PET film 6 was obtained in the same manner as PET film 1, except that the time for the cast film to pass through the stretching section in the machine direction was changed to 0.185 seconds and relaxation treatment after quenching was not performed. PET film 6 was produced under the same manufacturing conditions as PET film 4, but due to lot variation, its physical properties are slightly different from those of PET film 4.

[0190] 3-7.PET Film 7 As the PET film 7, a commercially available biaxially stretched PET film (product name "Cosmoshine A4160" manufactured by Toyobo Co., Ltd., thickness 38 μm, with an easy-adhesion layer on one side) was prepared.

[0191] 3-8.PET Film 8 As the PET film 8, a commercially available biaxially stretched PET film (product name "Cosmoshine A4160" manufactured by Toyobo Co., Ltd., thickness 38 μm, with an easy-adhesion layer on one side) was prepared.

[0192] 3-9.PET Film 9 Polyethylene terephthalate was melted at 290°C, extruded into a sheet through a film forming die, and cooled by contacting it with a water-cooled rotating quenching drum to produce an unstretched film. This unstretched film was preheated at 160°C for 150 seconds in a biaxial stretching tester (Toyo Seiki Co., Ltd.), and then stretched 5.2 times at 160°C in a fixed-end uniaxial manner to produce a PET film having in-plane birefringence. The refractive index of this PET film at a wavelength of 550 nm was nx=1.701, ny=1.6015, and Δn=0.0995. The thickness of this PET film was adjusted to obtain PET film 9, which was a uniaxially stretched PET film having an in-plane retardation of 5174 nm.

[0193] 4. Preparation of polyester film with adhesive layer and optical laminate [Example 1] The above-mentioned coating solution A for easy adhesion layer was applied onto a PET film 1 and dried at 90° C. for 60 seconds to form an easy adhesion layer having a thickness of 100 nm, thereby obtaining a polyester film with an easy adhesion layer of Example 1. Next, a coating solution for a hard coat layer having the following formulation was applied onto the easy-adhesion layer, dried at 80° C. for 60 seconds, and then exposed to ultraviolet light of 200 mJ / cm 2 The coating was cured by irradiation with UV light to form a hard coat layer having a dry thickness of 8 μm, thereby obtaining the optical layered body of Example 1.

[0194] <Coating solution for hard coat layer> Polyfunctional acrylate monomer 12 parts by weight (Nippon Kayakusha, product name: PET-30) Multifunctional acrylate oligomer 28 parts by weight (Mitsubishi Chemical Corporation, Product name: Shiko UV-1700B Toluene 48 parts by weight Methyl ethyl ketone 12 parts by weight

[0195] [Example 2] An optical laminate of Example 2 was obtained in the same manner as in Example 1, except that PET film 1 was changed to PET film 2 and coating liquid A for easy adhesion layer was changed to coating liquid B for easy adhesion layer.

[0196] [Example 3] An optical laminate of Example 3 was obtained in the same manner as in Example 1, except that the PET film 1 was changed to the PET film 3.

[0197] [Example 4] An optical laminate of Example 4 was obtained in the same manner as in Example 1, except that the PET film 1 was changed to the PET film 4.

[0198] [Example 5] An optical laminate of Example 5 was obtained in the same manner as in Example 1, except that Coating Liquid A for Easy-Adhesion Layer was changed to Coating Liquid F for Easy-Adhesion Layer.

[0199] [Example 6] An optical laminate of Example 6 was obtained in the same manner as in Example 1, except that Coating Liquid G for an Easy-Adhesion Layer was used instead of Coating Liquid A for an Easy-Adhesion Layer.

[0200] [Comparative Example 1] An optical laminate of Comparative Example 1 was obtained in the same manner as in Example 1, except that PET film 1 was changed to PET film 5, coating liquid A for the easy-adhesion layer was changed to coating liquid C for the easy-adhesion layer, and the drying conditions for the easy-adhesion layer were changed to 90°C for 120 seconds.

[0201] [Comparative Example 2] An optical laminate of Comparative Example 2 was obtained in the same manner as in Example 1, except that PET film 1 was changed to PET film 6 and coating liquid A for easy-adhesion layer was changed to coating liquid E for easy-adhesion layer.

[0202] [Comparative Example 3] An optical laminate of Comparative Example 3 was obtained in the same manner as in Example 1, except that the PET film 1 was changed to a PET film 7. The easy-adhesion layer and the hard coat layer were formed on the surface opposite to the easy-adhesion layer that had been formed in advance.

[0203] [Comparative Example 4] An optical laminate of Comparative Example 4 was obtained in the same manner as in Example 1, except that the PET film 1 was changed to the PET film 8 and the coating liquid for easy-adhesion layer A was changed to the coating liquid for easy-adhesion layer D. The easy-adhesion layer and the hard coat layer were formed on the surface opposite to the easy-adhesion layer that had been formed in advance.

[0204] [Comparative Example 5] An optical laminate of Comparative Example 5 was obtained in the same manner as in Example 1, except that PET film 1 was changed to PET film 9 and coating liquid A for easy-adhesion layer was changed to coating liquid E for easy-adhesion layer.

[0205] [Comparative Example 6] An optical laminate of Comparative Example 6 was obtained in the same manner as in Example 1, except that the drying conditions of the easy-adhesion layer were changed to 25°C for 180 seconds. In Comparative Example 6, the easy-adhesion layer was dried slowly, so that the thickness of the easy-adhesion layer was uneven. In the measurement of 1-2 above, the part with the smallest unevenness was used for evaluation, so that extremely uneven shapes were not included in the seven measurement areas.

[0206] [Table 1]

[0207] [Table 2]

[0208] From the results of Tables 1-2, it can be confirmed that the use of the polyester films with easy-adhesion layers of Examples 1-6 can improve the adhesion of the optical laminate having a polyester film with high pencil hardness, an easy-adhesion layer, and a functional layer in this order. The polyester film with easy-adhesion layer of Example 2 has a larger average value of δq / δa than the other Examples, so the adhesion was not as good as the other Examples. The reason why the average value of δq / δa of Example 2 is larger than the other Examples is thought to be because the ratio of the polyurethane component of the easy-adhesion layer is higher than the other Examples. The polyester film with easy-adhesion layer of Example 5 has a significantly smaller average value of δq / δa, so the adhesion was not as good as the other Examples. In Example 5, the component of the easy-adhesion layer is close to polyester alone, so it is thought that the average value of δq / δa is smaller because the viscoelasticity of the easy-adhesion layer approaches homogeneity. From the results of Tables 1 to 2, it can be confirmed that, when the polyester films with easy-adhesion layers of Comparative Examples 1 to 2 and 6 are used, the adhesion of the optical laminate having a polyester film with high pencil hardness, an easy-adhesion layer and a functional layer in this order cannot be made good. The reason is that the polyester films with easy-adhesion layers of Comparative Examples 1 to 2 and 6 have a pencil hardness of B or more, and the average value of δq / δa exceeds 1.60. The reason why the average value of δq / δa of Comparative Example 1 exceeds 1.60 is considered to be that the coating liquid for the easy-adhesion layer is aqueous, so it takes a long time to dry, and the resin component of the easy-adhesion layer is polyurethane. The reason why the average value of δq / δa of Comparative Example 2 exceeds 1.60 is considered to be that the resin component of the coating liquid for the easy-adhesion layer contains a polyurethane component and a polyester component, but the ratio of the polyurethane component is high. The reason why the average value of δq / δa of Comparative Example 6 exceeds 1.60 is considered to be that the coating liquid for the easy-adhesion layer takes a long time to dry. The polyester films with an easy-adhesion layer of Comparative Examples 3 to 5 had good adhesion, but since the pencil hardness of the polyester film was less than B, the surface of the functional layer of the optical laminate or the polyester film itself was easily scratched. Although not shown in Table 1, the optical layered bodies of Examples 1 to 4 all had a contact angle of 90 degrees with pure water on the surface having the hard coat layer. In addition, from the results in Tables 1 and 2, the average erosion rate (E 0-20 It can be seen that the PET films 1 to 6, in which the hardness is 1.4 μm / g or more, can easily have a pencil hardness of B or more. [Explanation of symbols]

[0209] 100: Polyester film 200: Easy adhesive layer 300: Functional layer 1000: Optical laminate 11: Container 12: Receptor 21: Test liquid piping 22: Compressed air piping 23: Return piping 24: Return pump 31, 32: Flowmeter 41, 42: Pressure gauge 50: Injection part 51: Nozzle 52: Cabinet 60: Cross-sectional profile acquisition section 70: Polyester film 81: Sample mounting stand 82:Support 90: Erosion rate measuring device A1: Water A2: Spherical silica A3: Air A4: Abraded polyester film

Claims

1. A polyester film having an easy-adhesion layer thereon, the polyester film is a biaxially stretched polyester film, the polyester film has a slow axis and a fast axis in a plane, and has a pencil hardness of B or more in the directions of the slow axis and the fast axis; The polyester film with an easy-adhesion layer, wherein the average value of δq / δa on the surface of the easy-adhesion layer is 1.125 or more and 1.60 or less. <Calculation of the average value of δq / δa> An area of ​​10 μm×10 μm on the surface of the easy-adhesion layer is measured using an atomic force microscope in phase mode. The phase signal distribution on the surface of the easy-adhesion layer is obtained by the above measurement. The unit of the phase signal is [deg]. The arithmetic mean value of the phase signal shown in the following formula 1 is denoted as δa, and the root mean square value of the phase signal shown in the following formula 2 is denoted as δq. (In the following formulas 1 and 2, the orthogonal coordinate axes X and Y are placed on a reference surface indicating the average value of the phase signal, the axis perpendicular to the reference surface is the Z axis, and the curved surface of the phase signal is f(x, y). In the following formulas 1 and 2, the sizes of the regions for calculating δa and δq are Lx and Ly. In the following formulas 1 and 2, Ar=Lx×Ly.) Seven regions of 2 μm×2 μm are selected from a measurement region of 10 μm×10 μm. δa, δq, and δq / δa at the seven regions are calculated. The average value of δq / δa is calculated based on δq / δa at five regions, excluding the maximum and minimum values ​​from the seven regions. [0010] [0025]

2. The polyester film with the easy-adhesion layer according to claim 1, wherein a coefficient of variation of δq / δa calculated based on δq / δa at the five positions is 0.009 or more and 0.040 or less.

3. The polyester film with an easy-adhesion layer according to claim 1, wherein nx is a refractive index in the slow axis direction in the plane of the polyester film, and ny is a refractive index in the direction perpendicular to the slow axis in the same plane, and nx and ny satisfy the following relationship. 0.0050≦nx−ny≦0.0250

4. The polyester film with an easy-adhesion layer according to claim 1 , wherein the thickness of the polyester film is from 10 μm to 75 μm.

5. The average erosion rate from the surface of the polyester film to a depth of 20 μm was E 0-20 When the E of the polyester film is defined as 0-20 The polyester film with an easy-adhesion layer according to claim 1, wherein the viscosity is 1.4 μm / g or more and 3.0 μm / g or less.

6. The polyester film with the easy-adhesion layer according to claim 1 , wherein the in-plane retardation of the polyester film is 450 nm or more and 1,200 nm or less.

7. The polyester film with an easy-adhesion layer according to claim 1 , wherein the easy-adhesion layer comprises a polyester component and a polyurethane component.

8. An optical laminate comprising the polyester film according to claim 1 and one or more functional layers on the easy-adhesion layer.

9. The optical laminate according to claim 8 , wherein the functional layer in contact with the easy-adhesion layer, among the one or more functional layers, contains a cured product of an ionizing radiation curable resin composition.

10. The optical laminate according to claim 8 , wherein the surface of the optical laminate having the functional layer has a contact angle with pure water of 80 degrees or more.

11. A polarizing plate having a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is an optical laminate described in any one of claims 8 to 10, and the optical laminate is arranged so that the surface on the functional layer side faces the opposite side to the polarizer.

12. A surface panel for an image display device, comprising an optical laminate bonded to a resin plate or a glass plate, the optical laminate being the optical laminate according to any one of claims 8 to 10, and the optical laminate being arranged so that the surface on the functional layer side faces the opposite side to the resin plate or the glass plate.

13. An image display device comprising the optical laminate according to any one of claims 8 to 10 disposed on a display element.

Citation Information

Patent Citations

  • Visibility improving method of liquid crystal display device, and liquid crystal display device using the same

    JP2011107198A

  • Polarizer protective film comprising biaxially oriented polyethylene terephthalate film

    JP2012032819A

  • Polarizing plate

    JP2016006530A

  • Polarizing plate, image display device, and method for manufacturing polarizing plate

    JP2019066716A

  • Laminate containing silica and application composition for forming porous silica layer

    WO2004073972A1